Slurry of diaphragm and coating, preparation method of slurry, preparation method of slurry, electrode assembly, battery and electric equipment

CN119404366APending Publication Date: 2025-02-07CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380044817.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-01-09
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The dendrite growth of metallic lithium in lithium batteries causes internal short circuits, affecting the safety and performance of the battery.

Method used

A separator is used, including a first isolation layer and a second isolation layer. A coating is provided on at least one surface of the first isolation layer. The coating contains a solid electrolyte material. The second isolation layer is provided on a surface of the coating away from the first isolation layer. to prevent lithium dendrites from penetrating the separator. The separator prevents the growth and side reactions of lithium dendrites by arranging a first isolation layer and a second isolation layer on both sides of the coating, and disposing the coating between the two isolation layers.

Benefits of technology

It effectively prevents lithium dendrites from penetrating the separator, improves the safety and performance of the battery, enhances the mechanical strength of the separator and the wettability of the electrolyte, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404366A_ABST
    Figure CN119404366A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of diaphragms, in particular to slurry of a diaphragm and a coating, preparation methods of the slurry, an electrode assembly, a battery and electric equipment. The diaphragm comprises a first isolation layer, a coating and a second isolation layer, the coating is arranged on at least one surface of the first isolation layer and comprises a solid electrolyte material, and the second isolation layer is arranged on the surface, away from the first isolation layer, of the coating. The solid electrolyte material can react with metal lithium to absorb lithium dendrites and prevent the lithium dendrites from penetrating through the diaphragm; the first isolation layer and the second isolation layer are arranged on the two sides of the coating respectively, lithium dendrites are prevented from penetrating through the diaphragm, the coating is arranged between the first isolation layer and the second isolation layer, and the coating is prevented from making contact with a cathode or an anode to generate side reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Slurry for diaphragm and coating and respective preparation methods, electrode assembly, battery and electrical equipment Technical Field

[0001] The present application relates to the field of diaphragm technology, and in particular to a slurry of a diaphragm and a coating and respective preparation methods, an electrode assembly, a battery and an electrical device. Background Art

[0002] Lithium batteries have higher energy density and can operate at higher voltages than other secondary batteries. Therefore, as secondary batteries that can be easily reduced in size and weight, they have been used in information devices such as mobile phones. In recent years, demand has also been growing for them as secondary batteries for large-scale powertrains such as electric vehicles and hybrid vehicles.

[0003] In lithium batteries, it is known that, depending on the battery configuration and usage, repeated charge and discharge cycles may cause dendrites of metallic lithium to grow from the negative electrode active material layer to the positive electrode active material layer, causing an internal short circuit.

[0004] Summary of the Invention

[0005] The main purpose of this application is to provide a diaphragm, which aims to prevent the dendrite growth of metallic lithium and improve the safety of battery use.

[0006] To achieve the above objectives, the present application proposes a diaphragm, comprising:

[0007] a first separator and a coating disposed on at least one surface of the first separator, the coating comprising a solid electrolyte material; and

[0008] A second isolation layer is provided on a surface of the coating layer away from the first isolation layer.

[0009] Optionally, the first isolation layer and / or the second isolation layer includes a base film.

[0010] Compared to inorganic material structures, the base film is lighter, which in turn reduces the weight of the separator, thereby avoiding a reduction in the mass energy density of the battery using the separator. It is understood that in one embodiment, the first separator layer includes the base film, while the second separator layer does not; in another embodiment, the first separator layer does not include the base film, while the second separator layer does; in another embodiment, both the first and second separator layers include the base film.

[0011] Optionally, the first isolation layer and / or the second isolation layer further includes an inorganic coating.

[0012] The inorganic coating has a certain hardness and can, to a certain extent, prevent lithium dendrites from penetrating the separator. The inorganic coating can provide overall mechanical strength to the separator, as well as improve the separator's insulation and wettability to the electrolyte. The first separator and / or the second separator also include an inorganic coating. It is understood that the first separator includes an inorganic coating, while the second separator does not; the first separator does not include an inorganic coating, while the second separator includes an inorganic coating; or both the first separator and the second separator include an inorganic coating.

[0013] Optionally, the first isolation layer includes a base film and an inorganic coating layer, and the inorganic coating layer is provided on at least one surface of the base film;

[0014] And / or, the second isolation layer includes a base film and an inorganic coating layer, and the inorganic coating layer is provided on at least one surface of the base film.

[0015] The base membrane is an organic microporous membrane. Compared with the inorganic coating, the organic microporous membrane is lighter, thereby reducing the weight of the diaphragm, thereby avoiding reducing the mass energy density of the battery using the diaphragm. The use of an isolation layer including a base membrane and an inorganic coating can reduce the thickness setting of the inorganic coating and improve the mass energy density of the battery.

[0016] Optionally, the coating has lithium ion conductivity. Optionally, at 25° C., the ion conductivity of the coating is in the range of 0.5 S / cm-5 S / cm.

[0017] The solid electrolyte material has lithium ion conductivity, which means that it has the ability to conduct ions. For example, it can be a solid electrolyte that can react with lithium metal and has the ability to conduct lithium ions. For example, the solid electrolyte material is a solid electrolyte containing Li, P, S and M, where M is Ge, Si, Sn or a combination thereof. The solid electrolyte material is Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 、Li 10 SnP2S 12 、Li 11 Si2PS 12 , Li4GeS4-Li3PS4 glass ceramics, Li-Si-PS-Cl solid electrolyte with LGPS type structure, or a combination thereof.

[0018] At 25°C, the ionic conductivity of the coating is in the range of 0.5 S / cm-5 S / cm. Within the above range, the ionic conductivity of the coating can be the maximum value, the minimum value, and any value between the maximum and the minimum values ​​of the above range, including but not limited to 0.5 S / cm, 0.8 S / cm, 1 S / cm, 1.5 S / cm, 1.8 S / cm, 2 S / cm, 2.5 S / cm, 2.8 S / cm, 3 S / cm, 3.5 S / cm, 3.8 S / cm, 4 S / cm, 4.5 S / cm, 4.8 S / cm, 5 S / cm, etc.

[0019] Optionally, the solid electrolyte material includes at least one of lithium titanium aluminum phosphate, lithium titanium phosphate, lithium tetrathiophosphate, lithium germanium phosphosulfur sulfide, and lithium phosphosulfur chloride.

[0020] The solid electrolyte material may include at least one of lithium aluminum titanium phosphate, lithium titanium phosphate, lithium tetrathiophosphate, lithium germanium phosphosulfur sulfide, and lithium phosphosulfur chloride. These substances are solid electrolyte materials with certain ionic conductivity and low electronic conductivity. When used as electrolyte materials, they have good ion conductivity and electronic insulation. Therefore, when used as a diaphragm coating, they will not significantly increase the diaphragm impedance and inhibit the transfer of electrons through the diaphragm. In addition, since such substances will undergo a gradual lithiation process after contact with lithium, accompanied by changes in the valence state of the transition metal element, when used as a diaphragm intermediate coating, they can react with lithium dendrites that pierce the diaphragm to prevent the lithium dendrites from continuing to grow.

[0021] Optionally, the particle size Dv50 of the solid electrolyte material is 50 nm-5 μm.

[0022] When the particle size of the solid electrolyte material powder is too large, the viscosity of the slurry is high during the slurry preparation process, and the uniformity is difficult to ensure, making it difficult to coat on the isolation layer. In addition, the "powder falling" phenomenon is prone to occur during the coating process, and the powder is difficult to adhere to the surface of the isolation layer, resulting in unsatisfactory coating effect and difficulty in achieving the expected effect. If the particle size is too small, during coating, the particles will block the pores on the surface of the isolation layer, reducing the permeability of the isolation layer, thereby blocking the ion conduction channel, resulting in a significant loss of battery capacity and cycle life. To this end, the particle size Dv50 of the solid electrolyte material is 50nm-5μm, for example, it can be 50nm, 100nm, 500nm, 800nm, 1μm, 2μm, 3μm, 4μm, 5μm, etc., that is, it can be any value within the range of 50nm-5μm, without specific limitation.

[0023] Optionally, the particle size Dv50 of the solid electrolyte material is 50 nm-500 nm.

[0024] When the particle size Dv50 of the solid electrolyte material is in the range of 50nm-500nm, the preparation effect and coating effect of the slurry are better. For example, the particle size Dv50 of the solid electrolyte material can be 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, etc., that is, it can be any value in the range of 50nm-500nm, and there is no specific limitation.

[0025] Optionally, the coating has a thickness of 0.5 μm-5 μm.

[0026] When the thickness of the coating is too large, the internal resistance of the diaphragm will increase, making it more difficult for lithium ions to be transmitted through the diaphragm, resulting in a decrease in battery performance. If the thickness of the coating is too small, the coating will absorb too little lithium, and when lithium dendrites grow in large quantities, the dendrites will penetrate the diaphragm. To this end, the thickness of the coating is 0.5μm-5μm, for example, it can be 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, etc., that is, it can be any value within the range of 0.5μm-5μm, without specific limitation.

[0027] Optionally, the thickness of the inorganic coating is 1 μm-5 μm.

[0028] The thickness of the inorganic coating should not be too thick or too thin. If the thickness of the inorganic coating is too thin, the supporting strength of the diaphragm will be insufficient and the electrolyte wettability will be poor. If the thickness of the inorganic coating is too thick, the energy density will be reduced. Therefore, the thickness of the inorganic coating is 1μm-5μm, for example, it can be 1μm, 2μm, 3μm, 4μm, 5μm, etc., that is, it can be any value within the range of 1μm-5μm, without specific limitation.

[0029] Optionally, the inorganic coating has a thickness of 1.5 μm-3.5 μm.

[0030] When the thickness of the inorganic coating is in the range of 1.5μm-3.5μm, the mechanical properties and wettability of the diaphragm are better. For example, the thickness of the inorganic coating is 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, etc., that is, it can be any value in the range of 1.5μm-3.5μm, without specific limitation.

[0031] Optionally, the inorganic material contained in the inorganic coating has a particle size Dv50 of 0.01 μm-10 μm.

[0032] The inorganic coating is made of inorganic materials. The particle size of the inorganic material affects the porosity and strength of the inorganic coating. When the particle size Dv50 of the inorganic material contained in the inorganic coating is 0.01μm-10μm, the mechanical properties and wettability of the inorganic coating are better. For example, the particle size Dv50 of the inorganic material contained in the porcelain layer is 0.01μm, 0.05μm, 0.1μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc., that is, it can be any value within the range of 0.01μm-10μm, and there is no specific limitation.

[0033] Optionally, the inorganic material contained in the inorganic coating has a particle size Dv50 of 0.05 μm-0.5 μm.

[0034] When the particle size Dv50 of the inorganic material contained in the inorganic coating is 0.05μm-0.5μm, the performance of the inorganic coating is better. For example, the particle size Dv50 of the inorganic material contained in the inorganic coating is 0.05μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, etc., that is, it can be any value within the range of 0.05μm-0.5μm, and there is no specific limitation.

[0035] Optionally, the inorganic material contained in the inorganic coating includes at least one of Al oxide, Al nitride, Si oxide, Si nitride, Fe oxide, Fe nitride, Fe oxychloride, Sn oxide, Ti oxide, Ti nitride, Cu oxide, Cu nitride, Mn oxide, Ge oxide, Zr oxide, Zn oxide, and Ni oxide.

[0036] The inorganic powder used in the inorganic coating is an inorganic particle suitable for use as the inorganic coating of the present application, and there is no particular limitation. Existing inorganic particles used in the field of diaphragms can be used, such as inorganic particles having good mechanical strength, high electrochemical stability, and good wettability to the electrolyte. For example, the inorganic material contained in the inorganic coating includes at least one of Al oxide, Al nitride, Si oxide, Si nitride, Fe oxide, Fe nitride, Fe oxyacid, Sn oxide, Ti oxide, Ti nitride, Cu oxide, Cu nitride, Mn oxide, Ge oxide, Zr oxide, Zn oxide, and Ni oxide.

[0037] Optionally, the inorganic material contained in the inorganic coating includes at least one of Al2O3, SiO2, ZnO, Fe2O3, NiO, CuO, and TiO2.

[0038] Cost-effective inorganic materials can save costs. For example, Al oxide includes Al2O3, Si oxide includes SiO2, Zn oxide includes ZnO, Fe oxide includes Fe2O3, Ni oxide includes NiO, Cu oxide includes CuO, and Ti oxide includes TiO2. Inorganic materials include at least one of Al2O3, SiO2, ZnO, Fe2O3, NiO, CuO, and TiO2.

[0039] It is understandable that the main components of the inorganic coating include nanoparticles of aluminum and silicon oxides. These nanoparticles make the diaphragm resistant to high temperatures, provide a hydrophilic surface, improve the electrolyte infiltration ability, promote the migration of active particles by interacting with anions in the electrolyte, and act as a barrier to prevent lithium dendrites from penetrating the diaphragm and causing battery short circuit.

[0040] Optionally, the base film has a thickness of 3 μm-30 μm.

[0041] If the thickness of the base film is too thin, the mechanical strength of the separator will be too poor, and it will be difficult to coat the electrolyte slurry on the base film. If the thickness of the base film is too thick, the internal resistance of the battery will increase. To this end, the thickness of the base film is 3μm-30μm, for example, it can be 3μm, 5μm, 7μm, 9μm, 10μm, 13μm, 15μm, 17μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, etc., that is, it can be any value within the range of 3μm-30μm, without specific limitation.

[0042] Optionally, the base film has a thickness of 5 μm-25 μm.

[0043] When the thickness of the base film is in the range of 5μm-25μm, the performance of the diaphragm is better. For example, the thickness of the base film can be 5μm, 6μm, 8μm, 11μm, 12μm, 14μm, 16μm, 18μm, 19μm, 20μm, 23μm, 25μm, etc., that is, it can be any value in the range of 5μm-25μm, and there is no specific limitation.

[0044] Optionally, the porosity of the base film is 40%-80%.

[0045] If the porosity of the base membrane is too small, the ion conductivity will be reduced. If the porosity of the base membrane is too large, the mechanical properties of the diaphragm will deteriorate. For this reason, the porosity of the base membrane is 40%-80%. For example, it can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc., that is, it can be any value within the range of 40%-80%, without specific limitation.

[0046] Optionally, the base film has a weight average molecular weight of 100,000-1,000,000.

[0047] Polymers with different weight-average molecular weights have different functions and uses. If the weight-average molecular weight is too much or too little, it is not within the weight-average molecular weight range of the base membrane used in lithium-ion batteries. The weight-average molecular weight of the base membrane used in lithium-ion batteries is 100,000-1,000,000. For example, it can be 100,000, 500,000, 800,000, 1,000,000, etc., that is, it can be any value within the range of 100,000-1,000,000, without specific limitation.

[0048] Optionally, the polymer material of the base film includes at least one of polypropylene, polyethylene, polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl chloride.

[0049] The base film can be selected from one of the polymer films such as polypropylene, polyethylene, and a non-woven film with polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, etc. as the matrix.

[0050] The present application also provides an electrode assembly, which includes an anode electrode piece, a cathode electrode piece, and the above-mentioned separator.

[0051] The electrode assembly formed by the above-mentioned diaphragm can prevent lithium dendrites from continuously growing and penetrating the diaphragm, thereby improving the safety of the electrode assembly.

[0052] Optionally, the first isolation layer is defined to face the anode electrode piece, and the second isolation layer is defined to face the cathode electrode piece. The first isolation layer includes a base film and an inorganic coating, and the inorganic coating is provided on a side of the base film away from the anode electrode piece.

[0053] Considering that the inorganic material contains certain active substances that react with lithium, in order to avoid the inorganic coating from directly contacting the lithium on the anode side and causing side reactions, the inorganic coating is arranged on the side with the base film facing the coating, that is, the inorganic coating is located between the base film and the coating.

[0054] Optionally, the first isolation layer faces the anode electrode piece, the second isolation layer faces the cathode electrode piece, the second isolation layer includes a base film and an inorganic coating, and the inorganic coating is arranged on the side of the base film facing the cathode electrode piece; and / or, the first isolation layer faces the anode electrode piece, the second isolation layer faces the cathode electrode piece, the second isolation layer includes a base film and an inorganic coating, and the inorganic coating is arranged on the side of the base film facing away from the cathode electrode piece.

[0055] That is, the inorganic coating is arranged on the side of the base membrane away from the coating; the base membrane is arranged on the side of the inorganic coating away from the coating; or the inorganic coating is arranged on both sides of the base membrane at the same time, further preventing dendrites from piercing the diaphragm, playing a protective role and improving the mechanical strength of the diaphragm.

[0056] The present application also provides a coating slurry, which includes a binder, a solvent, and a solid electrolyte material.

[0057] In the process of preparing the coating slurry, additives are generally added for better adhesion. For example, the coating slurry includes a binder solvent and a solid electrolyte material.

[0058] Optionally, the weight of the solid electrolyte material accounts for 30%-45% of the weight of the coating slurry;

[0059] And / or, the coating slurry further includes a dispersant and a thickener, and the ratio of the weight of the solid electrolyte material, the weight of the binder, the weight of the dispersant, and the weight of the thickener is 1:(0.15-0.45):(0.01-0.03):(0.15-0.35);

[0060] And / or, the weight of the solvent accounts for 30%-60% of the weight of the coating slurry.

[0061] A too low mass percentage of the solid electrolyte material results in a thinner slurry, increasing processing costs, while a high mass percentage results in a higher solid content, making processing difficult. Therefore, the weight of the solid electrolyte material accounts for 30%-45% of the weight of the coating slurry, for example, 30%, 33%, 35%, 38%, 40%, 42%, 43%, 44%, 45%, etc., that is, any value within the range of 30%-45% is not limited thereto.

[0062] The coating slurry also includes a dispersant and a thickener, and the weight ratio of the solid electrolyte material, the binder, the dispersant and the thickener is 1: (0.15-0.45): (0.01-0.03): (0.15-0.35).

[0063] The weight ratio of the solid electrolyte material to the binder is 1:(0.15-0.45). A moderate amount of binder can prevent the coating from falling off and has good heat resistance. Too little will result in insufficient adhesion, and too much will cause the slurry viscosity to exceed the standard. For this reason, the weight ratio of the solid electrolyte material to the binder is 1:(0.15-0.45), for example, it can be 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, etc., that is, it can be any value within the range of 1:(0.15-0.45), and is not specifically limited.

[0064] An appropriate dispersant content can ensure uniform dispersion of the slurry, while too low a content will cause the slurry to agglomerate and become difficult to disperse. To this end, the weight ratio of the solid electrolyte material to the dispersant is 1:(0.01-0.03), for example, it can be 1:0.01, 1:0.015, 1:0.02, 1:0.025, 0.03, etc., that is, it can be any value within the range of 1:(0.01-0.03), without specific limitation.

[0065] Too low a content of thickener leads to reduced slurry stability, while too high a content leads to excessive viscosity and difficulty in processing. To this end, the weight ratio of the solid electrolyte material to the thickener is 1:(0.15-0.35), for example, it can be 1:0.15, 1:0.19, 1:0.20, 1:0.25, 1:0.29, 1:0.30, 1:0.32, 1:0.35, etc., that is, it can be any value within the range of 1:(0.15-0.35), without specific limitation.

[0066] The weight of the solvent accounts for 30%-60% of the weight of the coating slurry. Too much solvent can easily cause the slurry to become thinner and the fluidity to be too high, making it inconvenient to operate during the coating process. For example, the slurry will easily flow on the isolation layer and be difficult to maintain. If the solvent is too low, the dispersion and viscosity of the slurry will deteriorate, which will not only make it inconvenient to coat, but also the coating effect after coating will be poor. For this reason, the weight of the solvent accounts for 30%-60% of the weight of the coating slurry. For example, it can be 30%, 34%, 39%, 40%, 44%, 49%, 50%, 54%, 56%, 58%, 60%, etc., that is, it can be any value within the range of 30%-60%, and there is no specific limitation.

[0067] Optionally, the binder includes at least one of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyvinylidene fluoride (PVDF);

[0068] and / or, the dispersant comprises at least one of hydrolyzed polymaleic anhydride, acrylic acid block polymer, polyester block polymer, polyethylene glycol type polyol and polyethyleneimine derivative;

[0069] And / or, the thickener includes at least one of sodium hydroxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyacrylate, polyurethane, and polyether;

[0070] And / or, the solvent includes at least one of deionized water, N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), N-dimethylacetamide (DMAC), and tetrahydrofuran (THF).

[0071] The binder includes at least one of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyvinylidene fluoride (PVDF). That is, the binder can be one of the above substances or a mixture of multiple substances.

[0072] The dispersant includes at least one of hydrolyzed polymaleic anhydride, acrylic acid block polymer, polyester block polymer, polyethylene glycol type polyol and polyethyleneimine derivative, that is, the dispersant can be one of the above substances or a mixture of multiple substances.

[0073] The thickener includes at least one of sodium hydroxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyacrylate, polyurethane, and polyether. That is, the thickener can be one of the above substances or a mixture of multiple substances.

[0074] The solvent includes at least one of deionized water, N-N dimethylformamide (DMF), N-N methylpyrrolidone (NMP), N-N dimethylacetamide (DMAC), and tetrahydrofuran (THF). That is, the solvent can be one of the above substances or a mixture of multiple substances. It is understood that when multiple substances are mixed, the multiple substances have good compatibility.

[0075] The present application provides a method for preparing a coating slurry, comprising the following steps:

[0076] The solid electrolyte material, binder and solvent are mixed evenly to obtain coating slurry.

[0077] The raw materials are blended and mixed evenly to obtain a slurry containing a coating of solid electrolyte material.

[0078] Optionally, the step of uniformly mixing the solid electrolyte material, the binder, and the solvent to obtain a coating slurry includes the following steps:

[0079] The solid electrolyte material, binder, dispersant, thickener and solvent are mixed evenly to obtain coating slurry.

[0080] In order to improve the dispersibility of the coating slurry, a dispersant and a thickener are added to the solid electrolyte material, the binder and the solvent and mixed.

[0081] Optionally, the step of uniformly mixing the solid electrolyte material, the binder, the dispersant, the thickener, and the solvent to obtain a coating slurry includes the following steps:

[0082] Putting the solid electrolyte material into a solvent, adding a dispersant for dispersion, and obtaining a dispersed solution;

[0083] adding a thickener to the dispersed solution for secondary dispersion treatment to obtain a secondary dispersed solution;

[0084] Then, a binder is added to the secondary dispersion solution and mixed to obtain a coating slurry.

[0085] In order to obtain a slurry with better uniformity and dispersion, each raw material is added in a step-by-step manner so that each raw material is fully dispersed, which is conducive to the uniform distribution of the solid electrolyte material in the coating finally prepared by coating on the isolation layer.

[0086] Optionally, in the step of adding a dispersant for dispersion, the dispersion method is ultrasonic dispersion; the ultrasonic dispersion time is 1h-3h, and / or the ultrasonic dispersion power range is 0.3W / cm 2 -0.6W / cm 2 , and / or, the frequency of the ultrasonic dispersion is 25kHz-40kHz.

[0087] Ultrasonic dispersion can achieve better mixing uniformity. Since the parameter setting of the ultrasonic equipment affects the dispersibility, controlling the parameters of the ultrasonic equipment within the following range is conducive to obtaining a better dispersion effect. The ultrasonic dispersion time is 1h-3h, for example, it can be 1h, 2h, 3h, etc., and there is no specific limitation. The power range of ultrasonic dispersion is 0.3W / cm 2 -0.6W / cm 2 , for example, it can be 0.3W / cm 2 , 0.4W / cm 2 , 0.5W / cm 2 , 0.6W / cm 2 etc., specifically not limited; the frequency of ultrasonic dispersion is 25kHz-40kHz, for example, it can be 25kHz, 30kHz, 35kHz, 38kHz, 40kHz, etc., specifically not limited.

[0088] Optionally, the step of adding a thickener to the dispersed solution for secondary dispersion treatment to obtain a secondary dispersed solution includes the following steps:

[0089] A thickener is added to the dispersed solution, and the mixture is stirred to obtain a secondary dispersed solution.

[0090] In order to fully mix the thickener with the solvent, the dispersant, and the solid electrolyte material, stirring is performed simultaneously in the step of adding the thickener to the dispersed solution.

[0091] Optionally, in the stirring step, the stirring speed is 1000 rpm-1600 rpm, and / or the stirring time is 30 min-90 min.

[0092] In order to fully mix the thickener with the solvent, dispersant and solid electrolyte material, stirring is performed simultaneously in the step of adding the thickener to the dispersed solution, and the stirring speed is 1000rpm-1600rpm, for example, it can be 1000rpm, 1100rpm, 1200rpm, 1300rpm, 1400rpm, 1500rpm, 1600rpm, etc., and the stirring time is 30min-90min, for example, it can be 30min, 40min, 50min, 60min, 70min, 80min, 90min, etc., to obtain a uniformly dispersed secondary dispersion solution.

[0093] Optionally, the step of adding a binder to the secondary dispersion solution and mixing to obtain a coating slurry includes the following steps:

[0094] Then, a binder is added to the secondary dispersion solution and stirred to obtain a coating slurry. In order to make the binder uniformly mixed in the secondary dispersion solution, the step of adding the binder to the secondary dispersion solution is stirred simultaneously.

[0095] Optionally, in the stirring step, the stirring speed is 700 rpm-1200 rpm, and / or the stirring time is 30 min-60 min.

[0096] The stirring speed is 700rpm-1200rpm, for example, it can be 700rpm, 800rpm, 900rpm, 1000rpm, 1100rpm, 1200rpm, etc., and the stirring time is 30min-60min, for example, it can be 30min, 40min, 50min, 60min, etc., to obtain a uniformly dispersed coating slurry.

[0097] The present application also provides a method for preparing a diaphragm, comprising the following steps:

[0098] preparing a first isolation layer and a second isolation layer, and applying a coating slurry on one of the first isolation layer and the second isolation layer;

[0099] Covering the other of the first isolation layer and the second isolation layer on the surface of the coating slurry away from one of the first isolation layer and the second isolation layer to obtain an interlayer film;

[0100] The interlayer film is subjected to heat pressing and drying to obtain a diaphragm.

[0101] In order to provide isolation layers on both sides of the coating, a first isolation layer and a second isolation layer are prepared, and the coating slurry is coated on one of the first isolation layer and the second isolation layer; the other of the first isolation layer and the second isolation layer is covered on the surface of the coating slurry away from one of the first isolation layer and the second isolation layer to obtain an interlayer film; the interlayer film is hot-pressed and dried to obtain a diaphragm.

[0102] Optionally, the two isolation layers are a first isolation layer and a second isolation layer, and the first isolation layer and / or the second isolation layer include a base film.

[0103] The base membrane is an organic microporous membrane, which is light in weight, thereby reducing the weight of the diaphragm, thereby avoiding reducing the mass energy density of the battery using the diaphragm.

[0104] Optionally, the first isolation layer and / or the second isolation layer further includes an inorganic coating.

[0105] The inorganic coating has a certain hardness and can prevent lithium dendrites from penetrating the diaphragm to a certain extent. The inorganic coating can provide the overall mechanical strength of the diaphragm, as well as improve the insulation of the diaphragm and improve the wettability of the diaphragm to the electrolyte.

[0106] Optionally, in the step of coating the coating slurry on one of the first isolation layer and the second isolation layer, the coating method is blade coating.

[0107] In the step of coating the slurry of the coating on the isolation layer, suitable conditions are required to prepare a qualified separator. For this purpose, the coating method used is blade coating to improve the coating effect.

[0108] Optionally, the method for preparing the diaphragm further satisfies at least one of conditions (1) to (3):

[0109] (1) In the step of obtaining the diaphragm after hot pressing and drying, the hot pressing temperature is 120° C. to 150° C.;

[0110] (2) In the step of obtaining the diaphragm after hot pressing and drying, the pressure of the hot pressing is 3 MPa-8 MPa;

[0111] (3) In the step of obtaining the diaphragm after hot pressing and drying, the drying conditions are drying under vacuum conditions, the drying temperature is 90° C.-120° C., and the drying time is 6 h-12 h.

[0112] The hot pressing temperature used in the hot pressing process is 120°C-150°C, for example, it can be 120°C, 130°C, 140°C, 150°C, etc., to obtain a better hot pressing effect.

[0113] The hot pressing pressure used in the hot pressing process is 3MPa-8MPa, for example, 3MPa, 4MPa, 5MPa, 6MPa, 7MPa, 8MPa, etc., to obtain a better hot pressing effect.

[0114] The drying conditions are vacuum conditions, the drying temperature is 90℃-120℃, for example, it can be 90℃, 100℃, 110℃, 120℃, etc., and the drying time is 6h-12h, for example, it can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc., to obtain better drying effect.

[0115] The present application also provides a battery comprising the electrode assembly.

[0116] Since the battery adopts the above-mentioned separator, the safety performance of the battery is improved.

[0117] The present application also provides an electrical device, which includes the battery.

[0118] Since the electrical equipment adopts the above-mentioned battery, the safety performance of the electrical equipment is improved.

[0119] The diaphragm of the present application includes a first isolation layer, a coating, and a second isolation layer. The coating is provided on at least one surface of the first isolation layer, and the coating comprises a solid electrolyte material. The second isolation layer is provided on a surface of the coating away from the first isolation layer. The solid electrolyte material reacts with metallic lithium, absorbing lithium dendrites and preventing them from penetrating the diaphragm. The first and second isolation layers are provided on either side of the coating to prevent lithium dendrites from penetrating the diaphragm. Furthermore, the coating is provided between the first and second isolation layers to prevent side reactions between the coating and the cathode or anode. BRIEF DESCRIPTION OF THE DRAWINGS

[0120] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0121] FIG1 is a schematic diagram of the preparation process of the coating slurry of the present application;

[0122] FIG2 is a schematic flow chart of a method for preparing a diaphragm according to the present application;

[0123] FIG3 is a schematic structural diagram of an embodiment of the diaphragm of the present application;

[0124] FIG4 is a schematic structural diagram of another embodiment of the diaphragm of the present application;

[0125] FIG5 is a schematic structural diagram of another embodiment of the diaphragm of the present application;

[0126] FIG6 is a schematic structural diagram of another embodiment of the diaphragm of the present application;

[0127] FIG7 is a schematic structural diagram of another embodiment of the diaphragm of the present application;

[0128] FIG8 is a schematic structural diagram of another embodiment of the diaphragm of the present application;

[0129] FIG9 is a schematic structural diagram of another embodiment of the diaphragm of the present application;

[0130] FIG10 is a schematic structural diagram of another embodiment of the diaphragm of the present application.

[0131] Description of Figure Numbers:

[0132] Reference number name Reference number name 100 diaphragm 20 isolation layer 10 coating 21 organic microporous membrane 11 first surface 23 ceramic layer 13 second surface

[0133] The realization of the objectives, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0134] The following will be combined with the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the embodiments described are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0135] It should be noted that all directional indications in the embodiments of the present application (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the various components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0136] In this application, unless otherwise specified or limited, the terms "connection" and "fixation" should be understood in a broad sense. For example, "fixation" can mean fixed connection, detachable connection, or integration; mechanical connection or electrical connection; direct connection or indirect connection through an intermediate medium; internal communication between two elements or interaction between two elements, unless otherwise specified. For those skilled in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0137] In addition, the descriptions of "first", "second", etc. in this application are only for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of such features. In addition, the meaning of "and / or" appearing throughout the text is to include three parallel solutions. Taking "A and / or B as an example", it includes solution A, or solution B, or a solution in which both A and B are satisfied. In addition, the technical solutions between the various embodiments can be combined with each other, but this must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by this application.

[0138] Batteries mentioned in this field can be categorized as either disposable or rechargeable, depending on whether they are rechargeable. Common rechargeable battery types include lead-acid batteries, nickel-metal hydride batteries, and lithium-ion batteries. Lithium-ion batteries are widely used in pure electric and hybrid vehicles. While these batteries have a relatively low capacity, they offer high output, high charging current, and a long service life, albeit at a relatively high cost.

[0139] The batteries described in the embodiments of this application are rechargeable batteries. The following description of the embodiments disclosed herein primarily uses lithium-ion batteries as an example. It should be understood that the embodiments disclosed herein are applicable to any other appropriate type of rechargeable battery. The batteries described in the embodiments disclosed herein can be directly or indirectly used in appropriate devices to power such devices.

[0140] The battery mentioned in the embodiments disclosed in this application refers to a single physical module that includes one or more battery cells to provide a predetermined voltage and capacity. Battery cells are the basic units in a battery and can generally be divided into cylindrical battery cells, rectangular battery cells, and soft-pack battery cells according to the packaging method. The following will mainly focus on rectangular battery cells. It should be understood that the embodiments described below are also applicable to cylindrical battery cells or soft-pack battery cells in some aspects.

[0141] A battery cell consists of a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. Lithium-ion battery cells primarily rely on the movement of lithium ions between the positive and negative electrode sheets. In cylindrical battery cells, a three-layer film structure is wound into a cylindrical electrode assembly, while in rectangular battery cells, the film structure is wound or stacked into a roughly rectangular electrode assembly.

[0142] In a typical battery cell structure, the battery cell includes a casing, an electrode assembly, and an electrolyte. The electrode assembly is housed in the battery cell casing and includes a positive electrode sheet, a negative electrode sheet, and a separator. The casing includes an outer shell and end caps. The outer shell includes a housing formed by multiple walls and an opening. The end caps are arranged at the opening to seal the housing. In addition to the electrode assembly, the housing cavity also contains electrolyte. The positive and negative electrode sheets in the electrode assembly include tabs. To ensure that high currents can pass without melting, the positive electrode tabs are multiple and stacked together, and the negative electrode tabs are multiple and stacked together. The tabs are electrically connected to electrode terminals located outside the battery cell via connecting members. The electrode terminals generally include positive and negative electrode terminals. For rectangular battery cells, the electrode terminals are generally located on the end caps. Multiple battery cells are connected in series and / or in parallel via the electrode terminals for various applications.

[0143] In high-power applications such as electric vehicles, batteries are used at three levels: cells, modules, and batteries. A battery module is a system of electrically connected cells placed within a frame to protect the cells from external shock, heat, and vibration. A battery is the final battery system installed in an electric vehicle. A battery typically includes a housing that encloses one or more cells. The housing typically consists of a lid and a shell.

[0144] A plurality of mounting points for connecting to the vehicle body are provided on the frame of the box or in the middle of the box shell. In order to improve the stability of the connection between the vehicle body and the battery, mounting parts are often provided at the mounting points.

[0145] In some battery production and processing technologies, multiple battery cells are first integrated into a battery module, and then the battery module is encapsulated in a battery box to form a battery pack / battery box.

[0146] A common battery module typically consists of two end plates, with multiple battery cells arranged between them. The end plate with the output terminal of the battery module is also called the output terminal plate, while the end plate without the output terminal is called the non-output terminal plate.

[0147] A battery pack can contain multiple battery modules in one row or multiple rows. The arrangement of multiple rows of battery modules can be double-row multiple-columns, multiple-row double-columns, or multiple-row multiple-columns. Taking a battery pack containing double-row multiple-columns as an example, the first end plate in each row is generally the head output extreme plate, the two adjacent end plates between two rows of battery modules are middle non-output extreme plates, and the last end plate in each row is the tail non-output extreme plate. The head output extreme plate and one of the middle non-output extreme plates belong to the first row of battery modules, while one of the middle non-output extreme plates and the tail output extreme plate belong to the second row of battery modules.

[0148] The packaging of battery modules into the battery box requires fixtures, which are typically equipped with gripping mechanisms such as claws or suction cups to hold the battery modules. When using fixtures with claws to package battery modules, claw grooves are typically provided on the side of the end plate facing away from the battery cells, allowing the claws to insert and securely hold the battery modules.

[0149] The development of battery technology must take into account multiple design factors at the same time, such as energy density, cycle life, discharge capacity, charge and discharge rate and other performance parameters. In addition, the production cost and processing technology of the battery must also be considered to improve the quality and production efficiency of the battery.

[0150] In lithium batteries, it is known that, depending on the battery configuration and usage, repeated charge and discharge cycles may cause dendrites of metallic lithium to grow from the negative electrode active material layer to the positive electrode active material layer, causing an internal short circuit.

[0151] It is understood here that lithium batteries include lithium metal batteries or lithium ion batteries.

[0152] In order to solve the above problems, the present application provides a diaphragm 100, which aims to prevent the dendrite growth of metallic lithium and improve the safety of battery use.

[0153] The diaphragm of the present application includes a first isolation layer, a coating and a second isolation layer. The first isolation layer is provided with a coating on at least one surface, the coating including a solid electrolyte material, and the second isolation layer is provided on a surface of the coating away from the first isolation layer.

[0154] The diaphragm is a key internal component in the structure of a lithium-ion battery. Its performance determines the battery's interface structure and internal resistance, directly impacting its capacity, cycle life, and safety. High-performance diaphragms are crucial for improving the battery's overall performance. The diaphragm's primary function is to separate the positive and negative electrodes of the battery, preventing contact and short circuits. It also allows electrolyte ions to pass through.

[0155] An isolation layer is a layer that separates structures on either side of the isolation layer to prevent direct contact between the structures on either side of the isolation layer. For example, the isolation layer can be an organic material layer or an inorganic material layer (for example, including but not limited to a ceramic layer), or a composite of an organic material layer and an inorganic material layer.

[0156] Anode. The battery electrode that releases electrons during the discharge process of an electrochemical cell is called the anode. For example, in a lithium-ion battery, the material on the anode side is a graphite layer.

[0157] Cathode, the electrode that absorbs electrons during the discharge process of the electrochemical cell is the cathode. For example, in a lithium-ion battery, the material on the cathode side can be a ternary material.

[0158] Electrolyte refers to a substance with the ability to conduct ions. For example, in a lithium-ion battery, the electrolyte exists in the separator and can conduct lithium ions back and forth between the positive and negative electrodes.

[0159] In lithium batteries, lithium dendrites growing on the anode side will penetrate the diaphragm, causing conduction between the positive and negative electrodes, which is dangerous. In the present application, the coating includes a solid electrolyte material, which can react with metallic lithium, thereby consuming metallic lithium and absorbing the lithium dendrites to prevent the lithium dendrites from continuing to grow and penetrate the diaphragm. In order to enhance the overall mechanical strength of the diaphragm, a first isolation layer and a second isolation layer are respectively provided on both sides of the coating to prevent lithium dendrites from penetrating the diaphragm, and the coating is provided between the first isolation layer and the second isolation layer to prevent the coating from contacting the cathode or anode to produce side reactions.

[0160] It is understandable that, as shown in FIG3 , an isolation layer 20 is provided on the side of the coating 10 facing the anode to prevent the solid electrolyte material in the coating 10 from directly contacting the Li metal on the anode side, causing excessive reaction and resulting in loss of lithium battery capacity.

[0161] It is understandable that in a lithium metal battery, when Li serves as the negative electrode, when the solid electrolyte material in the coating 10 contacts the Li negative electrode, the solid electrolyte material will react with the Li metal. Therefore, an isolation layer 20 is provided on the side of the coating 10 facing the anode to prevent the solid electrolyte material in the coating 10 from directly contacting the Li metal on the anode side, causing excessive reaction and resulting in loss of lithium battery capacity.

[0162] At the same time, in lithium-ion batteries, Li elements will also be deposited on the surface of the negative electrode, which is called dead lithium. In this case, when the solid electrolyte material in the coating 10 contacts the Li element, the solid electrolyte material will react with the Li element, causing the lithium battery capacity to be lost. Therefore, an isolation layer 20 is set on the side of the coating 10 facing the anode.

[0163] For example, as shown in FIG3 , the isolation layer 20 is provided on the first surface 11 of the coating 10 facing the anode side. It can be understood that, in some embodiments, if only a portion of the surface of the first surface 11 of the coating 10 is exposed with the solid electrolyte material, then the isolation layer 20 can be a hollow layered structure, and the isolation layer 20 is used to cover the solid electrolyte material exposed on the first surface 11.

[0164] Further, the first isolation layer and / or the second isolation layer includes a base film.

[0165] The base membrane is an organic microporous membrane, which refers to a membrane structure with micropores made of organic materials.

[0166] The organic microporous membrane is lightweight, thereby reducing the weight of the separator 100 , thereby avoiding a reduction in the mass energy density of the battery using the separator 100 .

[0167] It can be understood that, in one embodiment, the first isolation layer includes a base film, and the second isolation layer does not include a base film; in another embodiment, the first isolation layer does not include a base film, and the second isolation layer includes a base film; in another embodiment, both the first isolation layer and the second isolation layer include a base film.

[0168] Furthermore, the first isolation layer and / or the second isolation layer further includes an inorganic coating layer.

[0169] Inorganic coating refers to a structure including inorganic materials, such as but not limited to ceramic layers.

[0170] The inorganic coating has a certain hardness and can prevent lithium dendrites from penetrating the diaphragm to a certain extent. The inorganic coating can provide the overall mechanical strength of the diaphragm, as well as improve the insulation of the diaphragm and improve the wettability of the diaphragm to the electrolyte.

[0171] The first isolation layer and / or the second isolation layer also includes an inorganic coating. It can be understood that the first isolation layer includes an inorganic coating, and the second isolation layer does not include an inorganic coating; the first isolation layer does not include an inorganic coating, and the second isolation layer includes an inorganic coating; the first isolation layer and the second isolation layer both include an inorganic coating.

[0172] It can also be understood that the first isolation layer and the second isolation layer include a multi-layer structure, at least one layer in the multi-layer structure is an inorganic coating, and at least another layer is a layer of other materials, without specific limitation. For example, the multi-layer structure is a two-layer structure, one layer is an inorganic coating, and the other layer is an organic material layer; when the isolation layer does not include an inorganic coating, the isolation layer can be an organic material layer.

[0173] In one embodiment, as shown in FIG4 , the isolation layer 20 includes a ceramic layer 23. On the one hand, the ceramic layer 23 can prevent lithium dendrites from penetrating the diaphragm 100. The ceramic layer 23 has a certain hardness and can block lithium dendrites to a certain extent. On the other hand, the ceramic layer 23 can also improve the overall mechanical strength of the diaphragm 100, as well as improve the insulation of the diaphragm 100 and improve the wettability of the diaphragm 100 to the electrolyte.

[0174] Furthermore, the first isolation layer includes a base film and an inorganic coating, and the inorganic coating is provided on at least one surface of the base film; and / or the second isolation layer includes a base film and an inorganic coating, and the inorganic coating is provided on at least one surface of the base film.

[0175] The base membrane is an organic microporous membrane. Compared with the inorganic coating, the organic microporous membrane is lighter, thereby reducing the weight of the diaphragm, thereby avoiding reducing the mass energy density of the battery using the diaphragm. The use of an isolation layer including a base membrane and an inorganic coating can reduce the thickness setting of the inorganic coating and improve the mass energy density of the battery.

[0176] It can be understood that the first isolation layer includes a base film and an inorganic coating, and the inorganic coating is arranged on at least one surface of the base film. That is, with the coating 10 as a reference, the inorganic coating can be arranged on the side of the base film facing the coating 10, so that the inorganic coating is located between the coating 10 and the base film. The inorganic coating can also be arranged on the side of the base film away from the coating 10, so that the base film is located between the coating 10 and the inorganic coating. The specific setting method is not limited.

[0177] It can be understood that the second isolation layer includes a base film and an inorganic coating, and the inorganic coating is arranged on at least one surface of the base film. That is, with the coating 10 as a reference, the inorganic coating can be arranged on the side of the base film facing the coating 10, so that the inorganic coating is located between the coating 10 and the base film. The inorganic coating can also be arranged on the side of the base film away from the coating 10, so that the base film is located between the coating 10 and the inorganic coating. The specific setting method is not limited.

[0178] Taking into account that the inorganic material contains certain active substances that react with lithium, in order to avoid the inorganic coating from directly contacting the lithium on the anode side and causing side reactions, the inorganic coating is arranged on the side where the base membrane faces the coating, that is, the inorganic coating is located between the base membrane and the coating. For example, as shown in Figure 4, a ceramic layer is used as the inorganic coating, and an organic microporous membrane is used as the base membrane, and the ceramic layer 23 is arranged on the side of the organic microporous membrane 21 facing the first surface 11 of the coating 10.

[0179] That is, as shown in Figure 4, an organic microporous membrane 21 and a ceramic layer 23 are provided on the first surface 11 of the coating 10, and the ceramic layer 23 is provided on the side of the organic microporous membrane 21 facing the first surface 11, that is, the ceramic layer 23 is provided between the organic microporous membrane 21 and the coating 10. Since the ceramic contains a certain active substance that reacts with lithium, in order to prevent the ceramic layer 23 from directly contacting the lithium on the anode side and causing side reactions, the ceramic layer 23 is provided between the organic microporous membrane 21 and the coating 10 to prevent the ceramic layer 23 from directly contacting the lithium on the anode side. At the same time, the ceramic layer 23 is provided on the anode side but not in direct contact with the anode side, which can prevent dendrites from piercing the diaphragm and play a protective role. At the same time, the ceramic layer 23 can serve as an insulating layer to prevent the positive and negative electrodes from being conductive, while improving the mechanical strength of the diaphragm 100.

[0180] 5 and 6 , the diaphragm 100 further includes another isolation layer 20, which is disposed on the second surface 13 of the coating 10. It is understood that the first isolation layer and the second isolation layer as described above are disposed on two opposite surfaces of the coating 10, respectively.

[0181] In order to further improve the physical strength of the diaphragm and avoid direct contact between the coating 10 and the cathode side, the diaphragm 100 also includes another isolation layer 20, which is arranged on the second surface 13 of the coating 10, that is, as shown in Figure 5, the coating 10 is arranged between the two isolation layers 20.

[0182] As shown in FIG. 7 or FIG. 8 , the other isolation layer 20 includes a ceramic layer 23 .

[0183] Another isolation layer 20 includes a ceramic layer 23. On the one hand, the ceramic layer 23 can prevent lithium dendrites from penetrating the diaphragm 100. The ceramic layer 23 has a certain hardness and can block lithium dendrites to a certain extent. On the other hand, the ceramic layer 23 can also improve the overall mechanical strength of the diaphragm 100 and improve the insulation of the diaphragm 100.

[0184] As shown in FIG. 9 or FIG. 10 , another isolation layer 20 includes a ceramic layer 23 and an organic microporous membrane 21 .

[0185] Compared with the ceramic structure, the organic microporous membrane 21 is lighter, thereby reducing the weight of the diaphragm 100, thereby avoiding reducing the mass energy density of the battery using the diaphragm 100. The use of another isolation layer 20 including a ceramic layer 23 and an organic microporous membrane 21 can reduce the thickness setting of the ceramic layer 23 and improve the mass energy density of the battery.

[0186] As shown in FIG7 , the ceramic layer 23 is disposed on the side of the organic microporous membrane 21 facing away from the second surface 13 , that is, the ceramic layer 23 is disposed on the cathode side and is closest to the outer side. Placing the ceramic layer 23 on the cathode side can also prevent dendrites from piercing the diaphragm 100 , playing a final protective role. At the same time, the ceramic layer 23 can serve as an insulating layer to prevent conduction between the positive and negative electrodes. Furthermore, since the organic microporous membrane 21 has a strong hydrophobicity and poor affinity with highly polar electrolytes, the organic microporous membrane 21 is unable to absorb and retain electrolytes. The introduction of the hydrophilic ceramic layer 23 can effectively alleviate this problem. Placing the ceramic layer 23 on the outer side is conducive to absorbing and retaining electrolytes, and can further enhance the heat resistance and mechanical properties of the diaphragm 100 , thereby improving the performance and safety of the battery.

[0187] As shown in FIG8 , the organic microporous membrane 21 is disposed on the side of the ceramic layer 23 away from the second surface 13 , that is, the ceramic layer 23 is disposed between the coating 10 and the organic microporous membrane 21 . The ceramic layer 23 prevents dendrites from penetrating the diaphragm 100 and plays a protective role.

[0188] As shown in FIG7 , the ceramic layer 23 is disposed on the side of the organic microporous membrane 21 facing away from the second surface 13; as shown in FIG8 , the organic microporous membrane 21 is disposed on the side of the ceramic layer 23 facing away from the second surface 13; and as shown in FIG9 , ceramic layers 23 are disposed on both sides of the organic microporous membrane 21 to further prevent dendrites from piercing the separator 100, thereby providing protection and improving the mechanical strength of the separator 100. As shown in FIG10 , ceramic layers 23 may also be disposed on both the organic microporous membrane 21 on the first surface 11 and the second surface 13 of the coating 10 to further prevent dendrites from piercing the separator 100, thereby providing protection and improving the mechanical strength of the separator 100.

[0189] Furthermore, the polymer on the surface of the base film has polar functional groups, that is, the polymer on the surface of the organic microporous membrane 21 has polar functional groups.

[0190] In order to improve the adhesion between the organic microporous membrane 21 and the ceramic layer 23 or the surface of the coating 10, the polymer on the surface of the organic microporous membrane 21 carries polar functional groups, thereby increasing the surface energy, facilitating adhesion, and also facilitating the infiltration of the electrolyte. The polymer on the surface of the organic microporous membrane 21 can be activated by plasma surface modification or corona treatment, converting it from non-polar to polar, thereby increasing its surface energy.

[0191] Furthermore, the solid electrolyte material has lithium ion conductivity. Optionally, at 25° C., the ion conductivity of the coating is in the range of 0.5 S / cm-5 S / cm.

[0192] The solid electrolyte material has lithium ion conductivity, which means that it has the ability to conduct ions, that is, it can be a solid electrolyte that can react with lithium metal and also has the ability to conduct lithium ions. For example, the solid electrolyte material is a solid electrolyte containing Li, P, S and M, where M is Ge, Si, Sn or a combination thereof. The solid electrolyte material is Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 、Li 10 SnP2S 12 、Li 11 Si2PS 12 , Li4GeS4-Li3PS4 glass ceramics, Li-Si-PS-Cl solid electrolyte with LGPS type structure, or a combination thereof.

[0193] At 25°C, the ionic conductivity of the coating is in the range of 0.5 S / cm-5 S / cm. Within the above range, the ionic conductivity of the coating can be the maximum value, the minimum value, and any value between the maximum and the minimum values ​​of the above range, including but not limited to 0.5 S / cm, 0.8 S / cm, 1 S / cm, 1.5 S / cm, 1.8 S / cm, 2 S / cm, 2.5 S / cm, 2.8 S / cm, 3 S / cm, 3.5 S / cm, 3.8 S / cm, 4 S / cm, 4.5 S / cm, 4.8 S / cm, 5 S / cm, etc.

[0194] Furthermore, the solid electrolyte material includes at least one of lithium titanium aluminum phosphate, lithium titanium phosphate, lithium tetrathiophosphate, lithium germanium phosphosulfur sulfide, and lithium phosphosulfur chloride.

[0195] The solid electrolyte material may include at least one of lithium aluminum titanium phosphate, lithium titanium phosphate, lithium tetrathiophosphate, lithium germanium phosphosulfur sulfide, and lithium phosphosulfur chloride. These substances are solid electrolyte materials with certain ionic conductivity and low electronic conductivity. When used as electrolyte materials, they have good ion conductivity and electronic insulation. Therefore, when used as a diaphragm coating, they will not significantly increase the diaphragm impedance and inhibit the transfer of electrons through the diaphragm. In addition, since such substances will undergo a gradual lithiation process after contact with lithium, accompanied by changes in the valence state of the transition metal element, when used as a diaphragm intermediate coating, they can react with lithium dendrites that pierce the diaphragm to prevent the lithium dendrites from continuing to grow.

[0196] For example, taking lithium aluminum titanium phosphate as an example, lithium aluminum iron phosphate (LATP) as a solid electrolyte has a high ion conductivity. When lithium aluminum titanium phosphate is in direct contact with the anode side, LATP easily reacts with lithium metal, causing the Ti in LATP to 4+ Reduced to Ti 3+ , which leads to electron conduction in the lithium ion conductor LATP, thereby reducing the stability of LATP to the lithium sheet. Therefore, LATP is not suitable for direct use as a solid electrolyte. However, its high contact activity with lithium can be used as a separator coating to consume lithium dendrites growing on the anode side, thereby preventing dendrites from piercing the separator.

[0197] It is known that lithium aluminum titanium phosphate is currently used as a diaphragm coating slurry, and additives, thickeners and other auxiliary materials are added to achieve the purpose of improving the ionic conductivity of the diaphragm and replenishing lithium. When lithium aluminum iron phosphate is currently used as a diaphragm coating, it is directly exposed to the anode side. Since lithium aluminum iron phosphate and lithium are reactive, it is easy to react with the anode side when coated on one side, resulting in active lithium loss and electrolyte consumption. Therefore, the diaphragm 100 of the present application is used, and an isolation layer 20 is provided on the side of the coating 10 where the lithium aluminum iron phosphate is located facing the anode to prevent the lithium aluminum iron phosphate in the coating 10 from directly contacting the Li metal on the anode side, causing a transition reaction and resulting in lithium battery capacity loss.

[0198] The diaphragm 100 of the composite layer structure in the present application has an isolation layer 20 provided on the side of the coating 10 facing the anode. The lithium dendrites generated on the anode side will be absorbed by the above-mentioned solid electrolyte material when penetrating the isolation layer 20, thereby curbing the growth of the lithium dendrites and preventing the battery from short-circuiting. During the charge and discharge process of the lithium battery for several times, lithium dendrites are inevitably generated. The lithium dendrites continue to grow and eventually contact and pierce the isolation layer 20 on the anode side, and contact the solid electrolyte material in the coating 10. The components of the solid electrolyte material, such as lithium aluminum titanium phosphate and lithium titanium phosphate, can undergo redox reactions with Li, oxidize the Li element into Li ions and "store" them in the coating 10, absorbing the Li dendrites in time and avoiding further growth of the Li dendrites.

[0199] It can be understood that the material of the coating 10 can be entirely composed of the above-mentioned solid electrolyte material. In addition, in some cases, the coating 10 can also include other electrolyte materials that do not have the property of reacting with lithium metal. In some cases, the coating 10 can also include substances that can react with lithium metal but do not have ion conductivity. The specific solution to be adopted can be selected by those skilled in the art according to specific needs and is not limited here.

[0200] Furthermore, the particle size Dv50 of the solid electrolyte material is 50 nm-5 μm.

[0201] Dv50 is the particle size corresponding to the 50% cumulative particle size distribution percentage of a sample. Its physical meaning is that 50% of the particles are larger than this particle size, and 50% of the particles are smaller than this particle size. Dv50 is also called the median diameter or median particle size.

[0202] The Dv50 particle size distribution test involves adding an appropriate amount of the sample to be tested to a clean beaker, adding a surfactant dropwise and then a dispersant. Ultrasonication at 120W / 5 minutes ensures complete dispersion of the sample in the dispersant. The sample is then poured into the injection tower and circulated with the solution into the test optical system. The particles are illuminated by a laser beam, and the energy distribution of the scattered light is measured to determine the particle size distribution (shading degree: 8-12%).

[0203] When the particle size of the solid electrolyte material powder is too large, the viscosity of the slurry is high during the slurry preparation process, and the uniformity is difficult to ensure, making it difficult to coat on the isolation layer 20. In addition, the "powder falling" phenomenon is likely to occur during the coating process, and the powder is difficult to adhere to the surface of the isolation layer 20, resulting in an unsatisfactory coating effect and difficulty in achieving the expected effect. If the particle size is too small, during coating, the particles will block the pores on the surface of the isolation layer 20, reducing the air permeability of the isolation layer 20, thereby blocking the ion conduction channel, resulting in a significant loss of battery capacity and cycle life. For this reason, the particle size Dv50 of the solid electrolyte material is 50nm-5μm, for example, it can be 50nm, 100nm, 500nm, 800nm, 1μm, 2μm, 3μm, 4μm, 5μm, etc., that is, it can be any value within the range of 50nm-5μm, without specific limitation.

[0204] Furthermore, the particle size Dv50 of the solid electrolyte material is 50 nm-500 nm.

[0205] When the particle size Dv50 of the solid electrolyte material is in the range of 50nm-500nm, the preparation effect and coating effect of the slurry are better. For example, the particle size Dv50 of the solid electrolyte material can be 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, etc., that is, it can be any value in the range of 50nm-500nm, and there is no specific limitation.

[0206] Furthermore, the coating has a thickness of 0.5 μm-5 μm.

[0207] When the thickness of the coating is too large, the internal resistance of the diaphragm 100 will increase, making it more difficult for lithium ions to be transmitted through the diaphragm, resulting in a decrease in battery performance. If the thickness of the coating is too small, the coating will absorb too little lithium, and when lithium dendrites grow in large quantities, the dendrites will penetrate the diaphragm. To this end, the thickness of the coating is 0.5 μm-5 μm, for example, it can be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc., that is, it can be any value within the range of 0.5 μm-5 μm, without specific limitation.

[0208] Furthermore, the thickness of the inorganic coating layer is 1 μm-5 μm.

[0209] The thickness of the inorganic coating should not be too thick or too thin. If the thickness of the inorganic coating is too thin, the supporting strength of the diaphragm will be insufficient and the electrolyte wettability will be poor. If the thickness of the inorganic coating is too thick, the energy density will be reduced. Therefore, the thickness of the inorganic coating is 1μm-5μm, for example, it can be 1μm, 2μm, 3μm, 4μm, 5μm, etc., that is, it can be any value within the range of 1μm-5μm, without specific limitation.

[0210] It is understood that when the separator includes a plurality of inorganic coating layers, the thickness of the inorganic coating layer is the total thickness of the plurality of inorganic coating layers.

[0211] Furthermore, the thickness of the inorganic coating layer is 1.5 μm-3.5 μm.

[0212] When the thickness of the inorganic coating is in the range of 1.5μm-3.5μm, the mechanical properties and wettability of the diaphragm are better. For example, the thickness of the inorganic coating is 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, etc., that is, it can be any value in the range of 1.5μm-3.5μm, without specific limitation.

[0213] Furthermore, the inorganic material contained in the inorganic coating layer has a particle size Dv50 of 0.01 μm to 10 μm.

[0214] The inorganic coating is made of inorganic materials. The particle size of the inorganic material affects the porosity and strength of the inorganic coating. When the particle size Dv50 of the inorganic material contained in the inorganic coating is 0.01μm-10μm, the mechanical properties and wettability of the inorganic coating are better. For example, the particle size Dv50 of the inorganic material contained in the inorganic coating is 0.01μm, 0.05μm, 0.1μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc., that is, it can be any value within the range of 0.01μm-10μm, and there is no specific limitation.

[0215] Furthermore, the inorganic material contained in the inorganic coating layer has a particle size Dv50 of 0.05 μm to 0.5 μm.

[0216] When the particle size Dv50 of the inorganic material contained in the inorganic coating is 0.05μm-0.5μm, the performance of the inorganic coating is better. For example, the particle size Dv50 of the inorganic material contained in the inorganic coating is 0.05μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, etc., that is, it can be any value within the range of 0.05μm-0.5μm, and there is no specific limitation.

[0217] Furthermore, the inorganic material contained in the inorganic coating includes at least one of Al oxide, Al nitride, Si oxide, Si nitride, Fe oxide, Fe nitride, Fe oxychloride, Sn oxide, Ti oxide, Ti nitride, Cu oxide, Cu nitride, Mn oxide, Ge oxide, Zr oxide, Zn oxide, and Ni oxide.

[0218] The inorganic powder used in the inorganic coating is an inorganic particle suitable for use as the inorganic coating of the present application, and there is no particular limitation. Existing inorganic particles used in the field of diaphragms can be used, such as inorganic particles having good mechanical strength, high electrochemical stability, and good wettability to the electrolyte. For example, the inorganic material contained in the inorganic coating includes at least one of Al oxide, Al nitride, Si oxide, Si nitride, Fe oxide, Fe nitride, Fe oxyacid, Sn oxide, Ti oxide, Ti nitride, Cu oxide, Cu nitride, Mn oxide, Ge oxide, Zr oxide, Zn oxide, and Ni oxide.

[0219] Furthermore, the inorganic material contained in the inorganic coating includes at least one of Al2O3, SiO2, ZnO, Fe2O3, NiO, CuO, and TiO2.

[0220] Cost-effective inorganic materials can save costs. For example, Al oxide includes Al2O3, Si oxide includes SiO2, Zn oxide includes ZnO, Fe oxide includes Fe2O3, Ni oxide includes NiO, Cu oxide includes CuO, and Ti oxide includes TiO2. Inorganic materials include at least one of Al2O3, SiO2, ZnO, Fe2O3, NiO, CuO, and TiO2.

[0221] It is understandable that the main components of the inorganic coating include nanoparticles of aluminum and silicon oxides. These nanoparticles make the diaphragm resistant to high temperatures, provide a hydrophilic surface, improve the electrolyte infiltration ability, promote the migration of active particles by interacting with anions in the electrolyte, and act as a barrier to prevent lithium dendrites from penetrating the diaphragm and causing battery short circuit.

[0222] Furthermore, the base film has a thickness of 3 μm-30 μm.

[0223] If the thickness of the base film is too thin, the mechanical strength of the separator will be too poor, and it will be difficult to coat the electrolyte slurry on the base film. If the thickness of the base film is too thick, the internal resistance of the battery will increase. To this end, the thickness of the base film is 3μm-30μm, for example, it can be 3μm, 5μm, 7μm, 9μm, 10μm, 13μm, 15μm, 17μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, etc., that is, it can be any value within the range of 3μm-30μm, without specific limitation.

[0224] Furthermore, the thickness of the base film is 5 μm-25 μm.

[0225] When the thickness of the base film is in the range of 5μm-25μm, the performance of the diaphragm is better. For example, the thickness of the base film can be 5μm, 6μm, 8μm, 11μm, 12μm, 14μm, 16μm, 18μm, 19μm, 20μm, 23μm, 25μm, etc., that is, it can be any value in the range of 5μm-25μm, and there is no specific limitation.

[0226] Furthermore, the porosity of the base film is 40%-80%.

[0227] If the porosity of the base membrane is too small, the ion conductivity will be reduced. If the porosity of the base membrane is too large, the mechanical properties of the diaphragm will deteriorate. For this reason, the porosity of the base membrane is 40%-80%. For example, it can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc., that is, it can be any value within the range of 40%-80%, without specific limitation.

[0228] Furthermore, the base film has a weight average molecular weight of 100,000-1,000,000.

[0229] Polymers with different weight-average molecular weights have different functions and uses. If the weight-average molecular weight is too much or too little, it is not within the molecular weight range of the base membrane used in lithium-ion batteries. The weight-average molecular weight of the base membrane used in lithium-ion batteries is 100,000-1,000,000. For example, it can be 100,000, 500,000, 800,000, 1,000,000, etc., that is, it can be any value within the range of 100,000-1,000,000, without specific limitation.

[0230] Furthermore, the weight-averaged polymer material includes at least one of polypropylene, polyethylene, polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl chloride.

[0231] The weight can be selected from one of the polymer films such as polypropylene, polyethylene, and non-woven membranes based on polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, etc.

[0232] The present application also provides an electrode assembly comprising an anode electrode sheet, a cathode electrode sheet, and the aforementioned separator. The electrode assembly constructed with the aforementioned separator can prevent lithium dendrites from continuously growing and penetrating the separator, thereby improving the safety of the electrode assembly.

[0233] Furthermore, it is defined that the first isolation layer faces the anode electrode piece, and the second isolation layer faces the cathode electrode piece. When the first isolation layer includes a base film and an inorganic coating, the inorganic coating is arranged on the side of the base film away from the anode electrode piece.

[0234] Taking into account that the inorganic material contains certain active substances that react with lithium, in order to avoid the inorganic coating from directly contacting the lithium on the anode side and causing side reactions, the inorganic coating is arranged on the side where the base membrane faces the coating, that is, the inorganic coating is located between the base membrane and the coating. For example, as shown in Figure 4, a ceramic layer is used as the inorganic coating, and an organic microporous membrane is used as the base membrane, and the ceramic layer 23 is arranged on the side of the organic microporous membrane 21 facing the first surface 11 of the coating 10.

[0235] Furthermore, the first isolation layer faces the anode electrode, the second isolation layer faces the cathode electrode, the second isolation layer includes a base film and an inorganic coating, and the inorganic coating is arranged on the side of the base film facing the cathode electrode; and / or, the first isolation layer faces the anode electrode, the second isolation layer faces the cathode electrode, the second isolation layer includes a base film and an inorganic coating, and the inorganic coating is arranged on the side of the base film facing away from the cathode electrode.

[0236] That is, the inorganic coating is arranged on the side of the base film away from the coating; the base film is arranged on the side of the inorganic coating away from the coating; or the inorganic coating is arranged on both sides of the base film at the same time, further preventing dendrites from piercing the diaphragm 100, playing a protective role and improving the mechanical strength of the diaphragm 100.

[0237] The present application also provides a coating slurry, which includes a binder, a solvent and a solid electrolyte material.

[0238] In the process of preparing the coating slurry, additives are generally added for better adhesion. For example, the coating slurry includes a binder, a solvent, and a solid electrolyte material.

[0239] Furthermore, the weight of the solid electrolyte material accounts for 30%-45% of the weight of the coating slurry; and / or, the coating slurry also includes a dispersant and a thickener, and the ratio of the weight of the solid electrolyte material, the weight of the binder, the weight of the dispersant, and the weight of the thickener is 1: (0.15-0.45): (0.01-0.03): (0.15-0.35); and / or, the weight of the solvent accounts for 30%-60% of the weight of the coating slurry.

[0240] A too low mass percentage of the solid electrolyte material results in a thinner slurry, increasing processing costs, while a high mass percentage results in a higher solid content, making processing difficult. Therefore, the weight of the solid electrolyte material accounts for 30%-45% of the weight of the coating slurry, for example, 30%, 33%, 35%, 38%, 40%, 42%, 43%, 44%, 45%, etc., that is, any value within the range of 30%-45% is not limited thereto.

[0241] Furthermore, the weight of the solid electrolyte material accounts for 32%-40% of the weight of the coating slurry.

[0242] When the weight of the solid electrolyte material accounts for 32%-40% of the weight of the coating slurry, the performance of the slurry is better. For this reason, the weight of the solid electrolyte material can account for 32%, 34%, 36%, 37%, 39%, 40%, etc., that is, it can be any value within the range of 32%-40%, and there is no specific limitation.

[0243] The weight ratio of the solid electrolyte material, the binder, the dispersant and the thickener is 1: (0.15-0.45): (0.01-0.03): (0.15-0.35).

[0244] Furthermore, the weight ratio of the solid electrolyte material to the binder is 1:(0.15-0.45).

[0245] A moderate amount of binder can prevent the coating from falling off and has good heat resistance. Too little will result in insufficient adhesion, and too much will cause the slurry viscosity to exceed the standard. To this end, the weight ratio of the solid electrolyte material to the binder is 1:(0.15-0.45), for example, it can be 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, etc., that is, it can be any value within the range of 1:(0.15-0.45), without specific limitation.

[0246] Furthermore, the weight ratio of the solid electrolyte material to the binder is 1:(0.18-0.36).

[0247] When the weight ratio of the solid electrolyte material to the binder is 1:(0.18-0.36), the performance of the slurry is better. For this reason, the weight ratio of the solid electrolyte material to the binder can be 1:0.18, 1:0.22, 1:0.24, 1:0.26, 1:0.28, 1:0.32, 1:0.34, 1:0.36, etc., that is, it can be any value within the range of 1:(0.18-0.36), and is not specifically limited.

[0248] Furthermore, the weight ratio of the solid electrolyte material to the dispersant is 1:(0.01-0.03).

[0249] An appropriate dispersant content can ensure uniform dispersion of the slurry, while too low a content will cause the slurry to agglomerate and become difficult to disperse. To this end, the weight ratio of the solid electrolyte material to the dispersant is 1:(0.01-0.03), for example, it can be 1:0.01, 1:0.015, 1:0.02, 1:0.025, 0.03, etc., that is, it can be any value within the range of 1:(0.01-0.03), without specific limitation.

[0250] Furthermore, the weight ratio of the solid electrolyte material to the dispersant is 1:(0.015-0.025).

[0251] When the weight ratio of the solid electrolyte material to the dispersant is 1:(0.015-0.025), the performance of the slurry is better. For this reason, the weight ratio of the solid electrolyte material to the dispersant can be 1:0.015, 1:0.018, 1:0.021, 1:0.022, 1:0.024, 0.025, etc., that is, it can be any value within the range of 1:(0.015-0.025), and is not specifically limited.

[0252] Furthermore, the weight ratio of the solid electrolyte material to the thickener is 1:(0.15-0.35).

[0253] Too low a content of thickener leads to reduced slurry stability, while too high a content leads to excessive viscosity and difficulty in processing. To this end, the weight ratio of the solid electrolyte material to the thickener is 1:(0.15-0.35), for example, it can be 1:0.15, 1:0.19, 1:0.20, 1:0.25, 1:0.29, 1:0.30, 1:0.32, 1:0.35, etc., that is, it can be any value within the range of 1:(0.15-0.35), without specific limitation.

[0254] Furthermore, the weight ratio of the solid electrolyte material to the thickener is 1:(0.18-0.30).

[0255] When the weight ratio of the solid electrolyte material to the thickener is 1:(0.18-0.30), the performance of the slurry is better. For this reason, the weight ratio of the solid electrolyte material to the thickener can be 1:0.18, 1:0.20, 1:0.22, 1:0.24, 1:0.26, 1:0.28, 1:0.30, etc., that is, it can be any value within the range of 1:(0.18-0.30), and is not specifically limited.

[0256] Furthermore, the weight of the solvent accounts for 30% to 60% of the weight of the coating slurry.

[0257] Too much solvent can easily cause the slurry to become thinner and too fluid, making it difficult to operate during the slurry coating process. For example, the slurry will easily flow on the isolation layer 20 and be difficult to maintain. Too little solvent can cause the slurry to be less uniformly dispersed and less viscous, making coating inconvenient and the coating effect poor. Therefore, the weight of the solvent accounts for 30%-60% of the weight of the coating slurry. For example, it can be 30%, 34%, 39%, 40%, 44%, 49%, 50%, 54%, 56%, 58%, 60%, etc., that is, it can be any value within the range of 30%-60%, without specific limitation.

[0258] Furthermore, the weight of the solvent accounts for 45% to 55% of the weight of the coating slurry.

[0259] When the weight of the solvent accounts for 45%-55% of the weight of the coating slurry, the performance of the slurry is better. Therefore, it can be 45%, 46%, 48%, 50%, 52%, 53%, 55%, etc., without specific limitation.

[0260] Furthermore, the binder includes at least one of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyvinylidene fluoride (PVDF); and / or the dispersant includes at least one of hydrolyzed polymaleic anhydride, acrylic acid block polymer, polyester block polymer, polyethylene glycol type polyol, and polyethyleneimine derivative; and / or the thickener includes at least one of sodium hydroxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyacrylate, polyurethane, and polyether;

[0261] And / or, the solvent includes one of deionized water, N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), N-dimethylacetamide (DMAC), and tetrahydrofuran (THF).

[0262] The binder includes at least one of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyvinylidene fluoride (PVDF). That is, the binder can be one of the above substances or a mixture of multiple substances.

[0263] The dispersant includes at least one of hydrolyzed polymaleic anhydride, acrylic acid block polymer, polyester block polymer, polyethylene glycol type polyol and polyethyleneimine derivative, that is, the dispersant can be one of the above substances or a mixture of multiple substances.

[0264] The thickener includes at least one of sodium hydroxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyacrylate, polyurethane, and polyether. That is, the thickener can be one of the above substances or a mixture of multiple substances.

[0265] The solvent includes at least one of deionized water, N-N dimethylformamide (DMF), N-N methylpyrrolidone (NMP), N-N dimethylacetamide (DMAC), and tetrahydrofuran (THF). That is, the solvent can be one of the above substances or a mixture of multiple substances. It is understood that when multiple substances are mixed, the multiple substances have good compatibility.

[0266] The present application provides a method for preparing a coating slurry, comprising the following steps: uniformly mixing a solid electrolyte material, a binder, and a solvent to obtain a coating slurry.

[0267] As shown in the flow diagram of FIG1 , various raw materials are blended and evenly mixed to obtain a slurry containing a coating of a solid electrolyte material.

[0268] Furthermore, the step of uniformly mixing the solid electrolyte material, the binder, and the solvent to obtain the coating slurry includes the following steps: uniformly mixing the solid electrolyte material, the binder, the dispersant, the thickener, and the solvent to obtain the coating slurry.

[0269] In order to improve the dispersibility of the coating slurry, a dispersant and a thickener are added to the solid electrolyte material, the binder and the solvent and mixed.

[0270] Furthermore, the step of uniformly mixing the solid electrolyte material, the binder, the dispersant, the thickener, and the solvent to obtain a coating slurry includes the following steps: putting the solid electrolyte material into the solvent, adding the dispersant for dispersion to obtain a dispersed solution; adding the thickener to the dispersed solution for secondary dispersion treatment to obtain a secondary dispersed solution; and then adding the binder to the secondary dispersed solution for mixing to obtain a coating slurry.

[0271] In order to obtain a slurry with better uniformity and dispersion, each raw material is added in a step-by-step manner so that each raw material is fully dispersed, which is conducive to the uniform distribution of the solid electrolyte material in the coating finally prepared by coating on the isolation layer.

[0272] Furthermore, in the step of adding a dispersant for dispersion, the dispersion method is ultrasonic dispersion, the ultrasonic dispersion time is 1-3 hours, and / or the ultrasonic dispersion power range is 0.3W / cm 2 -0.6W / cm 2 , and / or, the frequency of ultrasonic dispersion is 25kHz-40kHz.

[0273] Ultrasonic dispersion can achieve better mixing uniformity. Since the parameter setting of the ultrasonic equipment affects the dispersibility, controlling the parameters of the ultrasonic equipment within the following range is conducive to obtaining a better dispersion effect. The ultrasonic dispersion time is 1h-3h, for example, it can be 1h, 2h, 3h, etc., and there is no specific limitation. The power range of ultrasonic dispersion is 0.3W / cm 2 -0.6W / cm 2 , for example, it can be 0.3W / cm 2 , 0.4W / cm 2 , 0.5W / cm 2 , 0.6W / cm 2 etc., specifically not limited; the frequency of ultrasonic dispersion is 25kHz-40kHz, for example, it can be 25kHz, 30kHz, 35kHz, 38kHz, 40kHz, etc., specifically not limited.

[0274] Furthermore, the step of adding a thickener to the dispersed solution for secondary dispersion treatment to obtain a secondary dispersed solution includes the following steps: adding a thickener to the dispersed solution and stirring to obtain a secondary dispersed solution.

[0275] In order to fully mix the thickener with the solvent, the dispersant, and the solid electrolyte material, stirring is performed simultaneously in the step of adding the thickener to the dispersed solution.

[0276] Furthermore, in the stirring step, the stirring speed is 1000 rpm-1600 rpm, and / or the stirring time is 30 min-90 min.

[0277] The stirring speed is 1000rpm-1600rpm, for example, it can be 1000rpm, 1100rpm, 1200rpm, 1300rpm, 1400rpm, 1500rpm, 1600rpm, etc., and the stirring time is 30min-90min, for example, it can be 30min, 40min, 50min, 60min, 70min, 80min, 90min, etc., to obtain a uniformly dispersed secondary dispersion solution.

[0278] Furthermore, the step of adding a binder to the secondary dispersion solution and mixing to obtain a coating slurry includes the following steps: adding a binder to the secondary dispersion solution and stirring to obtain a coating slurry.

[0279] In order to mix the binder uniformly in the secondary dispersion solution, stirring is performed simultaneously during the step of adding the binder to the secondary dispersion solution.

[0280] Furthermore, the stirring speed is 700 rpm-1200 rpm, and / or the stirring time is 30 min-60 min.

[0281] The stirring speed is 700rpm-1200rpm, for example, it can be 700rpm, 800rpm, 900rpm, 1000rpm, 1100rpm, 1200rpm, etc., and the stirring time is 30min-60min, for example, it can be 30min, 40min, 50min, 60min, etc., to obtain a uniformly dispersed coating slurry.

[0282] The present application provides a method for preparing a diaphragm, comprising the following steps: preparing a first isolation layer and a second isolation layer, coating a coating slurry on one of the first isolation layer and the second isolation layer; covering the other of the first isolation layer and the second isolation layer on a surface of the coating slurry away from one of the first isolation layer and the second isolation layer to obtain an interlayer film; and hot pressing and drying the interlayer film to obtain a diaphragm.

[0283] As shown in FIG2 , a flow chart of a method for preparing a diaphragm is provided. In order to provide isolation layers on both sides of the coating, a first isolation layer and a second isolation layer are prepared, and the coating slurry is coated on one of the first isolation layer and the second isolation layer; the other of the first isolation layer and the second isolation layer is covered on a surface of the coating slurry away from one of the first isolation layer and the second isolation layer to obtain an interlayer film; and the interlayer film is hot pressed and dried to obtain a diaphragm.

[0284] Furthermore, the two isolation layers are a first isolation layer and a second isolation layer, and the first isolation layer and / or the second isolation layer include a base film.

[0285] The base film is an organic microporous film, which is light in weight, thereby reducing the weight of the separator 100 , thereby avoiding reducing the mass energy density of the battery using the separator 100 .

[0286] Furthermore, the first isolation layer and / or the second isolation layer further includes an inorganic coating layer.

[0287] The inorganic coating has a certain hardness and can prevent lithium dendrites from penetrating the diaphragm to a certain extent. The inorganic coating can provide the overall mechanical strength of the diaphragm, as well as improve the insulation of the diaphragm and improve the wettability of the diaphragm to the electrolyte.

[0288] Furthermore, in the step of coating the coating slurry on the isolation layer 10, the coating method is knife coating.

[0289] In the step of coating the slurry of the coating on the isolation layer, suitable conditions are required to prepare a qualified separator. For this purpose, the coating method used is blade coating to improve the coating effect.

[0290] Furthermore, the preparation method of the diaphragm also satisfies at least one of conditions (1) to (3): (1) in the step of obtaining the diaphragm after hot pressing and drying, the hot pressing temperature is 120°C-150°C; (2) in the step of obtaining the diaphragm after hot pressing and drying, the hot pressing pressure is 3MPa-8MPa; (3) in the step of obtaining the diaphragm after hot pressing and drying, the drying conditions are drying under vacuum conditions, the drying temperature is 90°C-120°C, and the drying time is 6h-12h.

[0291] The hot pressing temperature used in the hot pressing process is 120°C-150°C, for example, it can be 120°C, 130°C, 140°C, 150°C, etc., to obtain a better hot pressing effect.

[0292] The hot pressing pressure used in the hot pressing process is 3MPa-8MPa, for example, 3MPa, 4MPa, 5MPa, 6MPa, 7MPa, 8MPa, etc., to obtain a better hot pressing effect.

[0293] The drying conditions are vacuum conditions, the drying temperature is 90℃-120℃, for example, it can be 90℃, 100℃, 110℃, 120℃, etc., and the drying time is 6h-12h, for example, it can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc., to obtain better drying effect.

[0294] Furthermore, the surface of the base film is subjected to plasma surface modification or corona treatment, so that the polymer on the surface of the base film has polar functional groups.

[0295] In order to improve the adhesion between the base film and the surface of the inorganic coating or coating 10, the polymer on the surface of the base film is activated by plasma surface modification or corona treatment, and is converted from non-polar to polar, thereby increasing its surface energy. The polymer on the surface of the base film carries polar functional groups, thereby increasing the surface energy, which is beneficial to adhesion and also facilitates the infiltration of the electrolyte.

[0296] The present application also provides a battery comprising the above-mentioned electrode assembly.

[0297] Since the electrode assembly adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0298] The present application also provides an electrical device, which includes the above-mentioned battery.

[0299] Since the battery adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0300] The positive electrode materials commonly used in lithium-ion batteries can be used in this application. The positive electrode active material involved in the positive electrode can be used to reversibly embed and de-embed Li + The compound, for example, can be Li x MO2 or Li y Lithium-containing composite oxides represented by M2O4 (wherein M is a transition metal, 0≤x≤1, 0≤y≤2), spinel oxides, layered metal chalcogenides, olivine structures, etc.

[0301] For example, lithium cobalt oxides such as LiCoO2, lithium manganese oxides such as LiMn2O4, lithium nickel oxides such as LiNiO2, Li 4 / 3 Ti 5 / 3 Lithium titanium oxides such as O4, lithium manganese nickel composite oxides, lithium manganese nickel cobalt composite oxides; and materials with olivine-type crystal structures such as LiMPO4 (M=Fe, Mn, Ni), etc.

[0302] In particular, lithium-containing composite oxides with layered or spinel structures are preferred, for example, LiCoO2, LiMn2O4, LiNiO2, LiNi 1 / 2 Mn 1 / 2 Lithium manganese nickel composite oxides represented by O2, LiNi l / 3 Mn 1 / 3 Co 1 / 3 O2、LiNi 0.6 Mn 0.2 Co 0.2 Lithium manganese nickel cobalt composite oxide represented by O2, or LiNi 1-x-y-z Co x Al y Mg z Lithium-containing composite oxides such as O2 (wherein 0≤x≤1, 0≤y≤0.1, 0≤z≤0.1, and 0≤1-xyz≤1). These include lithium-containing composite oxides in which a portion of the constituent elements of the aforementioned lithium-containing composite oxides are replaced with additive elements such as Ge, Ti, Zr, Mg, Al, Mo, and Sn.

[0303] These positive electrode active materials may be used alone or in combination of two or more. For example, by using a layered lithium-containing composite oxide and a spinel lithium-containing composite oxide simultaneously, both increased capacity and improved safety can be achieved.

[0304] The positive electrode used in non-aqueous electrolyte secondary batteries is prepared by, for example, appropriately adding a conductive additive such as carbon black or acetylene black, or a binder such as polyvinylidene fluoride or polyethylene oxide, to the aforementioned positive electrode active material to prepare a positive electrode mixture. This mixture is then coated onto a strip-shaped molded body having a current collector such as aluminum foil as a core material. However, the positive electrode production method is not limited to the above example.

[0305] The negative electrode materials commonly used in lithium-ion batteries can be used in this application. The negative electrode active material involved in the negative electrode can use a compound capable of intercalating and deintercalating lithium metal or lithium. For example, alloys or oxides of aluminum, silicon, tin, etc., carbon materials, and other materials can be used as the negative electrode active material. The carbon material can be graphite, pyrolytic carbon, coke, glassy carbon, sintered organic polymer compounds, mesophase carbon microbeads, etc.

[0306] The negative electrode used in non-aqueous electrolyte secondary batteries is prepared by, for example, appropriately adding a conductive additive such as carbon black or acetylene black, or a binder such as polyvinylidene fluoride or polyethylene oxide, to the aforementioned negative electrode active material to prepare a negative electrode mixture. This mixture is then coated onto a strip-shaped molded body having a current collector such as copper foil as a core material. However, the negative electrode production method is not limited to the above example.

[0307] In the non-aqueous electrolyte secondary battery provided by the present application, a non-aqueous solvent (organic solvent) is used as the non-aqueous electrolyte. Non-aqueous solvents include carbonates, ethers, and the like.

[0308] Carbonates comprise cyclic carbonates and chain carbonates, and cyclic carbonates can enumerate ethylene carbonate, propylene carbonate, butylene carbonate, gamma-butyrolactone, thioester (ethylene glycol sulfide etc.) etc. Chain carbonates can enumerate low-viscosity polar chain carbonates, aliphatic branched-chain carbonate compounds such as dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate etc. as representatives. A mixed solvent of cyclic carbonate (particularly ethylene carbonate) and chain carbonates is particularly preferred.

[0309] Examples of the ethers include tetraethylene glycol dimethyl ether (TEGDME), ethylene glycol dimethyl ether (DME), and 1,3-dioxolane (DOL).

[0310] In addition to the above-mentioned non-aqueous solvents, non-aqueous solvents (organic solvents) such as chain alkyl esters such as methyl propionate, chain triesters such as trimethyl phosphate, nitrile solvents such as 3-methoxypropionitrile, and branched compounds having ether bonds represented by dendrimers can be used.

[0311] In addition, fluorinated solvents can also be used.

[0312] As fluorine-based solvents, for example, H(CF2)2OCH3, C4F9OCH3, H(CF2)2OCH2CH3, H(CF2)2OCH2CF3, H(CF2)2CH2O(CF2)2H, or (perfluoroalkyl) alkyl ethers of linear structures such as CF3CHFCF2OCH3, CF3CHFCF2OCH2CH3, i.e., 2-trifluoromethylhexafluoropropyl methyl ether, 2-trifluoromethylhexafluoropropyl ethyl ether, 2-trifluoromethylhexafluoropropyl propyl ether, 3-trifluoromethyloctafluorobutyl methyl ether, 3-trifluoromethyloctafluorobutyl methyl ether, Methyl octafluorobutyl ethyl ether, 3-trifluoromethyl octafluorobutyl propyl ether, 4-trifluoromethyl decafluoropentyl methyl ether, 4-trifluoromethyl decafluoropentyl ethyl ether, 4-trifluoromethyl decafluoropentyl propyl ether, 5-trifluoromethyl dodecafluorohexyl methyl ether, 5-trifluoromethyl dodecafluorohexyl ethyl ether, 5-trifluoromethyl dodecafluorohexyl propyl ether, 6-trifluoromethyl tetradecafluoroheptyl methyl ether, 6-trifluoromethyl tetradecafluoroheptyl ethyl ether, 6-trifluoromethyl tetradecafluoroheptyl propyl ether, 7-trifluoromethyl hexadecafluorooctyl methyl ether, 7-trifluoromethyl hexadecafluorooctyl ethyl ether, 7-trifluoromethyl hexadecafluorooctyl propyl ether and the like.

[0313] Furthermore, the above-mentioned iso(perfluoroalkyl)alkyl ether and the above-mentioned linear (perfluoroalkyl)alkyl ether may be used in combination.

[0314] As the electrolyte salt used in the non-aqueous electrolyte solution, lithium salts such as lithium perchlorates, organoboron lithium salts, lithium salts of fluorine-containing compounds, and lithium imide salts are preferable.

[0315] Examples of such electrolyte salts include LiClO4, LiPF6, LiBF4, LiAsF6, LiSbF6, LiCF3SO3, LiCF3CO2, LiC2F4(SO3)2, LiN(C2F5SO2)2, LiC(CF3SO2)3, LiC n F 2n+1 SO3 (n ≥ 2), LiN(RfOSO2)2 (where Rf is a fluoroalkyl group), etc. Among these lithium salts, fluorinated organic lithium salts are particularly preferred. Fluorinated organic lithium salts are highly anionic and easily dissociate into ions, making them easily soluble in non-aqueous electrolytes.

[0316] The concentration of the electrolyte lithium salt in the non-aqueous electrolyte is preferably, for example, 0.3 mol / L (mole / liter) or higher, more preferably 0.7 mol / L or higher, preferably 1.7 mol / L or lower, and more preferably 1.2 mol / L or lower. If the concentration of the electrolyte lithium salt is too low, the ion conductivity is too low, while if it is too high, there is a concern that the electrolyte salt may not be completely dissolved and may precipitate.

[0317] Furthermore, various additives that can improve the performance of batteries using the non-aqueous electrolyte may be added to the non-aqueous electrolyte, without particular limitation.

[0318] In particular, this application can also be used in lithium metal batteries, replacing traditional separators. The negative electrode can be lithium metal or a lithium alloy, or no negative electrode is required. The corresponding positive electrode materials are as described above. For lithium metal batteries without a negative electrode, the positive electrode material requires a lithium source.

[0319] Since the pole piece adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0320] Example

[0321] Example 1

[0322] Diaphragm preparation

[0323] 1) A polyethylene porous membrane (organic microporous membrane) with a thickness of 7 μm was sequentially cleaned with ethanol or acetone, dried at 60° C. to 70° C., flattened, and then plasma treated for 4 minutes for use.

[0324] 2) preparing a coating slurry, the coating slurry comprising LATP, a binder polyvinylidene fluoride (PVDF), a dispersant hydrolyzed polymaleic anhydride, a thickener sodium hydroxymethyl cellulose (CMC), and deionized water, in a mass ratio of LATP:PVDF:hydrolyzed polymaleic anhydride:sodium hydroxymethyl cellulose:solvent = 0.35:0.07:0.0056:0.0875:0.4869.

[0325] 3) Based on the total mass of the coating slurry being 100%, 35% by mass of lithium aluminum titanium phosphate inorganic particles, 0.56% by mass of hydrolyzed polymaleic anhydride dispersant, and 48.69% by mass of deionized water were mixed and ultrasonically dispersed in an ultrasonic cleaning machine for 2 hours.

[0326] 4) After the dispersion is completed, the thickener CMC is slowly added to continue the secondary dispersion, and the dispersion is carried out at a speed of 1000 rpm for 30 minutes. After the stirring is completed, the binder PVDF is added for secondary mixing, and the mixture is stirred at 800 rpm for 30 minutes to form a coating slurry. The coating slurry is coated on one side of a polyethylene porous membrane with a porosity of 60% and a thickness of 7 μm by gravure transfer coating. The coating thickness is 3 μm. Then, the non-coated side of the Al2O3 ceramic composite membrane (CCS, purchased from Shanghai Enjie) is composited with it and baked at 60°C for 5 minutes to obtain the membrane.

[0327] Example 2

[0328] The process was the same as in Example 1 except that the ratio of LATP:PVDF:hydrolyzed polymaleic anhydride:sodium hydroxymethylcellulose:solvent in 2) was changed to 0.32:0.064:0.0052:0.08:0.5308.

[0329] Example 3

[0330] The process was the same as in Example 1 except that the ratio of LATP:PVDF:hydrolyzed polymaleic anhydride:sodium hydroxymethylcellulose:solvent in 2) was changed to 0.4:0.08:0.0064:0.1:0.4136.

[0331] Example 4

[0332] The process was the same as in Example 1 except that the ratio of LATP:PVDF:hydrolyzed polymaleic anhydride:sodium hydroxymethylcellulose:solvent in 2) was changed to 0.3:0.06:0.0048:0.075:0.5602.

[0333] Example 5

[0334] The process was the same as in Example 1 except that the ratio of LATP:PVDF:hydrolyzed polymaleic anhydride:sodium hydroxymethylcellulose:solvent in 2) was changed to 0.45:0.09:0.0072:0.1125:0.3403.

[0335] Example 6

[0336] Except that the solid electrolyte powder used in 2) is changed to lithium titanium phosphate (LTP), the rest is the same as in Example 1.

[0337] Example 7

[0338] Except that the solid electrolyte powder used in 2) is changed to lithium tetrathiophosphate (Li3PS4), the rest is the same as Example 1.

[0339] Example 8

[0340] Except for the solid electrolyte powder used in 2) is changed to lithium germanium phosphosulfide (Li 10 GeP2S 12 , LGPS), the rest is the same as Example 1.

[0341] Example 9

[0342] Except that the Al2O3 ceramic composite diaphragm used in 4) is replaced with a boehmite ceramic composite diaphragm, the rest is the same as in Example 1.

[0343] Example 10

[0344] Except that the Al2O3 ceramic composite diaphragm used in 4) is replaced with a SiO2 ceramic composite diaphragm, the rest is the same as in Example 1.

[0345] Example 11

[0346] Except that the solid electrolyte powder used in 2) is changed to Li6PS5Cl, the rest is the same as Example 1.

[0347] Example 12-Example 14

[0348] Except that the size of the solid electrolyte powder used in 2) is changed to 50 nm, 500 nm, and 5 μm, the rest is the same as in Example 1.

[0349] Example 15-Example 16

[0350] Except that the thickness of the solid electrolyte coating used in 2) is changed to 0.5 μm and 5 μm, the rest is the same as Example 1.

[0351] Example 17-Example 20

[0352] Except that the thickness of the ceramic composite diaphragm used in 4) is changed to 1 μm, 1.5 μm, 3.5 μm and 5 μm, the rest is the same as Example 1.

[0353] Example 21-Example 24

[0354] Except that the particle size Dv50 of the inorganic material of the ceramic composite diaphragm used in 4) is changed to 0.01 μm, 0.05 μm, 0.5 μm and 10 μm, the rest is the same as Example 1.

[0355] Comparative Example 1

[0356] The process was the same as in Example 1 except that the ratio of LATP:PVDF:hydrolyzed polymaleic anhydride:sodium hydroxymethylcellulose:solvent in 2) was changed to 0.2:0.04:0.0032:0.05:0.7068.

[0357] Comparative Example 2

[0358] The process was the same as in Example 1 except that the ratio of LATP:PVDF:hydrolyzed polymaleic anhydride:sodium hydroxymethylcellulose:solvent in 2) was changed to 0.5:0.1:0.008:0.125:0.267.

[0359] Comparative Example 3

[0360] Except that the solid electrolyte powder used in 2) is changed to Al2O3, the rest is the same as Example 1.

[0361] Comparative Example 4-Comparative Example 5

[0362] Except that the size of the solid electrolyte powder used in 2) is changed to 40 nm and 6000 nm, the rest is the same as Example 1.

[0363] Comparative Example 6-Comparative Example 7

[0364] Except that the thickness of the solid electrolyte coating used in 2) is changed to 0.4 μm and 6 μm, the rest is the same as Example 1.

[0365] Comparative Example 8-Comparative Example 9

[0366] Except that the thickness of the ceramic composite diaphragm used in 4) is changed to 0.5 μm and 6 μm, the rest is the same as that of Example 1.

[0367] Table 1 Parameter list of the embodiment

[0368]

[0369] Table 2 Parameter list of the embodiment

[0370]

[0371] Table 3 Parameter list of the embodiment

[0372]

[0373]

[0374] Table 4 Parameter list of the embodiment

[0375]

[0376]

[0377] Table 5 Comparative Example Parameters

[0378]

[0379] Table 6 Comparative Example Experiment Parameters

[0380]

[0381] Diaphragm performance test, the test results are listed in Table 7 and Table 8

[0382] 1) Diaphragm puncture strength test

[0383] According to the national standard GB / T 36363-2018 Polyolefin separators for lithium-ion batteries, the lithium battery separator is flattened in a fixture and clamped. It is punctured at a rate of (100+10) mm / min. After completion, the sample is removed and the thickness is tested at four points around the pinhole in accordance with the provisions of GB / T 6672-2001. The average value is taken and the puncture strength is calculated.

[0384] 2) Wettability test of diaphragm

[0385] The test membrane was cut into a size of 50mm×50mm, and 1ml of standard electrolyte (1M LiPF6 dissolved in ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a weight ratio of 1:1:1 was dropped on the sample. The angle between the droplet and the membrane was observed using a contact angle meter.

[0386] 3) Electrolyte absorption rate test of diaphragm

[0387] Soak the separator in the electrolyte for 60 minutes. Take it out every 10 minutes to dry and measure the separator weight. The electrolyte absorption rate can be calculated as (diaphragm weight after absorption - initial separator weight) / initial separator weight. The higher the electrolyte absorption rate, the better the separator's wettability.

[0388] 4) Diaphragm ion conductivity test

[0389] The test was carried out in accordance with the standard GB / T36363-2018.

[0390] 5) Discharge rate test of isolation film

[0391] A discharge rate test was performed using a button cell battery. The positive electrode of the battery used lithium iron phosphate, wherein the ratio of lithium iron phosphate: conductive carbon black: PVDF binder was 8:1:1. The negative electrode used a lithium sheet, the electrolyte used 1M LiFSI / DME, and the separator used was the separator of the embodiment and the comparative example, wherein the ceramic layer of the separator faced the positive electrode of the battery, and the side of the separator that had been corona treated faced the negative electrode of the battery.

[0392] Charging conditions: The battery was charged at room temperature using the constant current-constant voltage (CC-CV) mode. First, the battery was charged in CC mode at a constant current of 0.33C until the voltage reached 3.65V. The battery was then switched to constant voltage mode with a cutoff current of 0.05C to fully charge.

[0393] Discharge conditions: Discharge to 2.5V in constant current mode at different discharge rates (0.33C / 1C / 2C) and cycle 100 times.

[0394] Calculate and record the coulombic efficiency (discharge capacity / charge capacity*100%) at different discharge rates after 100 cycles.

[0395] Table 7 Performance parameter list

[0396]

[0397]

[0398] Table 8 Discharge rate performance

[0399]

[0400]

[0401] Data Analysis

[0402] As shown in Table 7, the thickness of the composite diaphragms provided in Examples 1 to 10 of this application is in the range of 18 μm to 23 μm, and the puncture strength is not less than 9.57 N·μm -1 , the wetting angle is not higher than 18°, the electrolyte absorption rate is not lower than 196%, and the ion conductivity is not lower than 1.62mS / cm, indicating that the composite diaphragm provided in this application has good mechanical strength, electrolyte wetting ability and ion conducting performance.

[0403] As shown in Table 8, the coulombic efficiency of the diaphragms in the examples is better than that of the comparative examples, indicating that the dendrite resistance and capacity retention of the diaphragms in the examples are better than those of the diaphragms used in the comparative examples, regardless of low-rate or high-rate current cycling.

[0404] The above are only preferred embodiments of the present application and are not intended to limit the patent scope of the present application. All equivalent structural transformations made using the contents of the present application specification and drawings under the inventive concept of the present application, or direct / indirect applications in other related technical fields are included in the patent protection scope of the present application.

Claims

1. A diaphragm, characterized in that: The diaphragm comprises: a first separator and a coating disposed on at least one surface of the first separator, the coating comprising a solid electrolyte material; and A second isolation layer is disposed on a surface of the coating layer away from the first isolation layer.

2. The diaphragm according to claim 1, characterized in that The first isolation layer and / or the second isolation layer includes a base film.

3. The diaphragm according to claim 1 or 2, characterized in that: The first isolation layer and / or the second isolation layer further comprises an inorganic coating layer.

4. The diaphragm according to claim 3, characterized in that The first isolation layer includes a base film and an inorganic coating layer, wherein the inorganic coating layer is disposed on at least one surface of the base film; And / or, the second isolation layer includes a base film and an inorganic coating layer, and the inorganic coating layer is disposed on at least one surface of the base film.

5. The diaphragm according to any one of claims 1 to 4, characterized in that The coating has lithium ion conductivity. Optionally, at 25° C., the ion conductivity of the coating is in the range of 0.5 S / cm-5 S / cm.

6. The diaphragm according to any one of claims 1 to 5, characterized in that The solid electrolyte material includes at least one of lithium aluminum titanium phosphate, lithium titanium phosphate, lithium tetrathiophosphate, lithium germanium phosphosulfur sulfide, and lithium phosphosulfur chloride.

7. The diaphragm according to any one of claims 1 or 6, characterized in that The particle size Dv50 of the solid electrolyte material is 50nm-5μm.

8. The diaphragm according to claim 7, characterized in that The particle size Dv50 of the solid electrolyte material is 50nm-500nm.

9. The diaphragm according to any one of claims 1 to 8, characterized in that The coating has a thickness of 0.5 μm-5 μm.

10. The diaphragm according to any one of claims 3 to 9, characterized in that The thickness of the inorganic coating is 1 μm-5 μm.

11. The diaphragm according to claim 10, characterized in that The thickness of the inorganic coating is 1.5 μm-3.5 μm.

12. The diaphragm according to any one of claims 3 to 11, characterized in that The inorganic coating layer contains an inorganic material having a particle size Dv50 of 0.01 μm to 10 μm.

13. The diaphragm according to claim 12, characterized in that The inorganic coating layer contains an inorganic material having a particle size Dv50 of 0.05 μm to 0.5 μm.

14. The diaphragm according to any one of claims 3 to 13, characterized in that The inorganic material contained in the inorganic coating includes at least one of Al oxide, Al nitride, Si oxide, Si nitride, Fe oxide, Fe nitride, Fe oxyacid, Sn oxide, Ti oxide, Ti nitride, Cu oxide, Cu nitride, Mn oxide, Ge oxide, Zr oxide, Zn oxide and Ni oxide.

15. The diaphragm according to any one of claims 3 to 14, characterized in that The inorganic material contained in the inorganic coating includes at least one of Al2O3, SiO2, ZnO, Fe2O3, NiO, CuO, and TiO2.

16. The diaphragm according to any one of claims 2 to 15, characterized in that The base film has a thickness of 3 μm-30 μm.

17. The diaphragm according to claim 16, characterized in that The base film has a thickness of 5 μm-25 μm.

18. The diaphragm according to any one of claims 2 to 17, characterized in that The porosity of the base film is 40%-80%.

19. The diaphragm according to any one of claims 2 to 18, characterized in that The weight average molecular weight of the base film is 100,000-1,000,000.

20. The diaphragm according to any one of claims 2 to 19, characterized in that The polymer material of the base film includes at least one of polypropylene, polyethylene, polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl chloride.

21. An electrode assembly, characterized in that: The electrode assembly comprises an anode electrode piece, a cathode electrode piece, and a separator as claimed in any one of claims 1 to 20.

22. The electrode assembly according to claim 21, characterized in that It is defined that the first isolation layer faces the anode electrode piece, the second isolation layer faces the cathode electrode piece, the first isolation layer includes a base film and an inorganic coating, and the inorganic coating is arranged on a side of the base film away from the anode electrode piece.

23. The electrode assembly according to claim 21 or 22, characterized in that: The first isolation layer faces the anode electrode piece, the second isolation layer faces the cathode electrode piece, the second isolation layer comprises a base film and an inorganic coating, and the inorganic coating is arranged on a side of the base film facing the cathode electrode piece; And / or, the first isolation layer faces the anode electrode plate, the second isolation layer faces the cathode electrode plate, the second isolation layer includes a base film and an inorganic coating, and the inorganic coating is arranged on a side of the base film away from the cathode electrode plate.

24. A slurry for a coating as claimed in any one of claims 1 to 20, characterized in that The coating slurry includes a binder, a solvent and a solid electrolyte material.

25. The coating slurry according to claim 24, characterized in that The weight of the solid electrolyte material accounts for 30%-45% of the weight of the coating slurry; And / or, the coating slurry further comprises a dispersant and a thickener, and the ratio of the weight of the solid electrolyte material, the weight of the binder, the weight of the dispersant, and the weight of the thickener is 1: (0.15-0.45): (0.01-0.03): (0.15-0.35); And / or, the weight of the solvent accounts for 30%-60% of the weight of the slurry of the coating.

26. The coating slurry according to claim 25, characterized in that The binder includes at least one of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyvinylidene fluoride (PVDF); and / or, the dispersant comprises at least one of hydrolyzed polymaleic anhydride, acrylic acid block polymer, polyester block polymer, polyethylene glycol type polyol and polyethyleneimine derivative; And / or, the thickener includes at least one of sodium hydroxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyacrylate, polyurethane, and polyether; And / or, the solvent includes at least one of deionized water, N-N dimethylformamide (DMF), N-N methylpyrrolidone (NMP), N-N dimethylacetamide (DMAC), and tetrahydrofuran (THF).

27. A method for preparing a coating slurry, characterized in that: The following steps are involved: The solid electrolyte material, the binder and the solvent are mixed evenly to obtain a coating slurry.

28. The method for preparing a coating slurry according to claim 27, characterized in that: The step of uniformly mixing the solid electrolyte material, the binder and the solvent to obtain the coating slurry includes the following steps: The solid electrolyte material, binder, dispersant, thickener and solvent are mixed evenly to obtain coating slurry.

29. The method for preparing a coating slurry according to claim 28, characterized in that: The step of uniformly mixing the solid electrolyte material, the binder, the dispersant, the thickener and the solvent to obtain the coating slurry includes the following steps: Putting the solid electrolyte material into a solvent, adding a dispersant for dispersion, and obtaining a dispersed solution; adding a thickener to the dispersed solution for secondary dispersion treatment to obtain a secondary dispersed solution; Then, a binder is added to the secondary dispersion solution and mixed to obtain a coating slurry.

30. The method for preparing a coating slurry according to claim 29, characterized in that: In the step of adding a dispersant for dispersion, the dispersion method is ultrasonic dispersion; The ultrasonic dispersion time is 1h-3h, and / or the ultrasonic dispersion power range is 0.3W / cm 2 -0.6W / cm 2 , and / or, the frequency of the ultrasonic dispersion is 25kHz-40kHz.

31. The method for preparing a coating slurry according to claim 29, characterized in that: The step of adding a thickener to the dispersed solution for secondary dispersion treatment to obtain a secondary dispersed solution comprises the following steps: A thickener is added to the dispersed solution, and the mixture is stirred to obtain a secondary dispersed solution.

32. The method for preparing a coating slurry according to claim 31, characterized in that: In the stirring step, the stirring speed is 1000 rpm-1600 rpm, and / or the stirring time is 30 min-90 min.

33. The method for preparing a coating slurry according to claim 29, characterized in that: The step of adding a binder to the secondary dispersion solution and mixing to obtain a coating slurry comprises the following steps: Then, a binder is added to the secondary dispersion solution, and the mixture is stirred to obtain a coating slurry.

34. The method for preparing a coating slurry according to claim 33, characterized in that: In the stirring step, the stirring speed is 700 rpm-1200 rpm, and / or the stirring time is 30 min-60 min.

35. A method for preparing a diaphragm according to any one of claims 1 to 20, characterized in that: The following steps are involved: preparing a first isolation layer and a second isolation layer, and applying a coating slurry on one of the first isolation layer and the second isolation layer; Covering the other of the first isolation layer and the second isolation layer on the surface of the slurry of the coating layer away from the surface of the first isolation layer and the second isolation layer to obtain an interlayer film; The interlayer film is subjected to heat pressing and drying to obtain a diaphragm.

36. The method for preparing a diaphragm according to claim 35, characterized in that: The two isolation layers are a first isolation layer and a second isolation layer, and the first isolation layer and / or the second isolation layer include a base film.

37. The method for preparing a diaphragm according to claim 35 or 36, characterized in that: The first isolation layer and / or the second isolation layer further comprises an inorganic coating layer.

38. The method for preparing a diaphragm according to any one of claims 35 to 37, characterized in that: In the step of coating the coating slurry on one of the first isolation layer and the second isolation layer, the coating method is knife coating.

39. The method for preparing a diaphragm according to any one of claims 35 to 38, characterized in that: The method for preparing the diaphragm further satisfies at least one of conditions (1) to (3): (1) In the step of obtaining a diaphragm after hot pressing and drying, the temperature of the hot pressing is 120° C.-150° C.; (2) In the step of obtaining the diaphragm after hot pressing and drying, the pressure of the hot pressing is 3MPa-8MPa; (3) In the step of obtaining the diaphragm after hot pressing and drying, the drying conditions are drying under vacuum conditions, the drying temperature is 90° C.-120° C., and the drying time is 6 h-12 h.

40. A battery, characterized in that: Comprising the electrode assembly as claimed in any one of claims 21 to 23.

41. An electrical equipment, characterized in that: The electrical device comprises a battery as claimed in claim 51.